Polymeric electrolytes containing soluble organometallic complexes and their preparation and use

CN123018118APending Publication Date: 2026-10-30INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510564019.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是,该技术用到的大量新型填料,成本高昂,不利于产业化生产

Benefits of technology

[0039]本发明提供了一种含可溶性有机金属络合物的聚合物电解质,具备优异的电化学性能和界面稳定性。通过将具有表面活性位点的可溶性有机金属络合物以分子级别均匀分散于聚合物基体中,不仅有效避免了传统无机填料在聚合物电解质中易团聚、分散不均及界面接触差的问题,而且显著提高了有机金属络合物与聚合物链段及锂盐之间的路易斯酸碱作用效率。具体而言,通过有机金属络合物中的金属中心离子作为路易斯酸,与聚合物链段中的醚氧基等路易斯碱性基团或锂盐阴离子发生配位作用,从而调控锂离子的传输,促进锂盐阴离子分解并在电极界面形成稳定的界面膜,有效抑制副反应的发生。得益于上述作用机制,本发明的聚合物电解质不仅可以实现较高的离子电导率(~0.1mS·cm-1)和宽电压窗口(>4.5V),还能显著改善聚合物电解质与电极之间的固固界面接触问题,增强了电解质的热稳定性和电化学稳定性,从而提升了固态电池的循环性能和使用寿命。此外,通过控制有机金属络合物在聚合物基体中的质量百分比(3%-10%),实现其在聚合物电解质体系中的高效作用,进一步保证了聚合物电解质的性能优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018118A_ABST
    Figure CN123018118A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of polymer electrolyte containing soluble organic metal complex and its preparation and application.Polymer electrolyte containing soluble organic metal complex includes: polymer matrix, lithium salt and organic metal complex;Wherein, the organic metal complex is uniformly distributed in polymer matrix, forms the mixing of molecular level;The mass ratio of the organic metal complex and the polymer matrix is 3:100-10:100;The surface of the organic metal complex has active site, and the active site acts as lewis acid, and the polymer chain segment of polymer matrix or the anion in lithium salt as lewis base occurs, forms coordination structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, and more particularly to a polymer electrolyte containing a soluble organometallic complex, its preparation and application. Background Technology

[0002] In recent years, solid-state batteries have attracted increasing attention due to their high specific energy, long lifespan, and high safety. As a core component of solid-state batteries, the development of solid-state electrolytes has also received significant attention within the industry.

[0003] Polymer electrolytes have attracted considerable attention as a class of solid-state electrolyte materials with great commercial potential due to their advantages in flexibility, processability, cost-effectiveness, and environmental friendliness. Since M. Armand proposed polyethylene oxide (PEO)-based polymer electrolytes in 1971, various all-solid-state or quasi-solid-state polymer electrolyte systems have been gradually developed. Polymer-based electrolytes can be mass-produced using current battery production lines due to their compatibility with existing battery manufacturing processes and assembly methods. However, their relatively low ionic conductivity (<0.1 mS / cm) is a significant drawback. -1 The narrow electrochemical window (<4.5V) and other factors greatly limit the performance of polymer electrolytes, making them unable to meet the increasing demands for energy density and fast charging.

[0004] To address the aforementioned problems of polymer electrolytes, numerous studies have optimized them using two techniques: adding plasticizers or inorganic fillers. Adding plasticizers to polymer electrolytes introduces a small amount of liquid phase into the all-solid-state battery, but significantly improves ionic conductivity, and selecting suitable high-voltage resistant plasticizers can greatly broaden the voltage window. Adding inorganic fillers to polymer electrolytes, through organic-inorganic interactions, can construct interconnected high-ionic-conductivity pathways within the polymer matrix and stabilize polymer segments, thus simultaneously improving ionic conductivity, broadening the electrochemical window, and enhancing mechanical properties—an effective method for improving polymer electrolyte performance. Through these two methods, the ionic conductivity of polymer electrolytes has been effectively improved (>0.1 mS / cm). -1 It also effectively widens the high voltage window (>4.5V).

[0005] However, commonly used methods for modifying polymer electrolytes with plasticizers and fillers still have certain problems. For example, the introduction of plasticizers increases the liquid phase component in solid-state electrolytes. If there is too much, it can pose safety hazards to solid-state batteries, leading to poor cycle performance and a significant decrease in cycle life, as well as a substantial reduction in the mechanical strength of the polymer electrolyte material. Furthermore, while most plasticizers can broaden the electrochemical window, they can trigger some side reactions unrelated to electrochemistry. For instance, succinate (SN) can cause severe side reactions on the lithium metal side, resulting in a significant decrease in the performance of the lithium metal anode. Adding inorganic fillers to polymer electrolytes often fails to disperse effectively, leading to a reduction in the organic-inorganic interface contact area and poor interfacial performance, while also reducing batch-to-batch consistency.

[0006] The literature (Liquid Metal Loaded Molecular Sieve: Specialized Lithium Dendrite Blocking Filler for Polymeric Solid-State Electrolyte, ADVANCED MATERIALS, 36(21)) proposes integrating molecular sieves (MS) as inert fillers and liquid metals (LM) as functional modules into PEO to form an "LM-MS-PEO" composite material, which can yield polymer solid electrolytes with improved ionic conductivity. However, the large number of novel fillers used in this technology are costly and not conducive to industrial production.

[0007] In summary, existing methods of adding plasticizers and inorganic fillers to polymer electrolytes have not completely solved the problems of severe interfacial side reactions, poor mechanical properties, poor solid-solid contact, and poor cycle performance caused by safety hazards in polymer electrolytes. It is difficult to improve ionic conductivity and achieve a high voltage window while taking into account solid-solid interface performance, mechanical properties, contact interface chemical properties, and safety performance, which limits the application of polymer electrolytes in high-energy-density batteries. Summary of the Invention

[0008] The purpose of this invention is to address the shortcomings of existing technologies by providing a polymer electrolyte containing a soluble organometallic complex, its preparation, and its application. This invention introduces a soluble organometallic complex additive with numerous active sites on its surface into the polymer electrolyte. This achieves high ionic conductivity and a high voltage window while effectively improving solid-solid interface contact, suppressing interfacial side reactions, and significantly enhancing mechanical properties, battery cycle performance, and cycle life.

[0009] To achieve the above objectives, in a first aspect, the present invention provides a polymer electrolyte containing a soluble organometallic complex, comprising: a polymer matrix, a lithium salt, and an organometallic complex;

[0010] The organometallic complex is uniformly distributed in the polymer matrix, forming a molecular-level mixture; the mass ratio of the organometallic complex to the polymer matrix is ​​3:100-10:100.

[0011] The surface of the organometallic complex has active sites, which act as Lewis acids and interact with polymer segments or anions in lithium salts that are Lewis bases to form coordination structures.

[0012] Preferably, the organometallic complex includes one or more of the following: acetylacetone complex, isopropanol complex, and ethoxylated compound;

[0013] The polymer matrix includes one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), polyvinylidene chloride (PVDC), poly(polyethylene glycol monomethyl ether) (PEGMEA), polyaramid, polyimide, polyvinylidene fluoride, polytetrafluoroethylene, or single-ion conductor polymer electrolytes (SICPEs).

[0014] The lithium salt includes one or more of inorganic lithium salts or organic lithium salts; the lithium salt is preferably a lithium salt containing a sulfonyl group and / or a carbonyl group; more preferably, the lithium salt specifically includes one or more of lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate; the mass ratio of the lithium salt to the polymer matrix is ​​30:100-100:100.

[0015] Preferably, the organometallic complex includes an acetylacetone complex; more preferably, the acetylacetone complex specifically includes one or more of aluminum acetylacetone, nickel acetylacetone, copper acetylacetone, zinc acetylacetone, and zirconium acetylacetone.

[0016] Preferably, the polymer electrolyte further includes a supporting material; the supporting material includes one or more of the following: a base membrane, nonwoven fabric, glass fiber, and fiber composite material; the supporting material is preferably a porous supporting material, more preferably a porous base membrane; the porosity of the porous supporting material is 50%-90%; and / or,

[0017] The polymer electrolyte further includes one or more of the following: film-forming agent, plasticizer, and filler;

[0018] The film-forming agent includes one or more of fluoroethylene carbonate (FEC), lithium difluorooxalate borate (LiDFOB), and lithium difluorophosphate; the mass ratio of the film-forming agent to the polymer matrix is ​​3:100-10:100.

[0019] The plasticizer includes one or more of succinic acid, tetraethylene glycol dimethyl ether, ethylene carbonate EC, ethylene ethylene carbonate VEC, ethylene ethylene carbonate VC, N,N-dimethylformamide DMF, and N,N-dimethylacetamide DMAc; the mass ratio of the plasticizer to the polymer matrix is ​​15:100-40:100.

[0020] The filler includes inorganic fillers and / or organic fillers; specifically, it includes active fillers and / or inert fillers, wherein the active filler is an inorganic solid electrolyte with ion-conducting capability, including one or more of perovskite type, NASICON type, garnet type, oxide glass and sulfide glass; the inert filler is a material without ion-conducting capability, including one or more of SiO2, ZrO2, Al2O3, TiO2, clay, metal-organic framework compound (MOF), covalent organic framework (COF); the mass ratio of the filler to the polymer matrix is ​​1:100-60:100.

[0021] In a second aspect, embodiments of the present invention provide a method for preparing the polymer electrolyte containing a soluble organometallic complex as described in the first aspect above, the preparation method comprising: solution casting or in-situ polymerization;

[0022] The solution casting method includes: uniformly mixing a polymer matrix, lithium salt, organometallic complex, and solvent in a mass ratio of 100:30-100:3-10:1000-2000 to form a polymer solution, and drying the polymer solution to obtain the polymer electrolyte; wherein the organometallic complex is dissolved in the polymer solution;

[0023] The in-situ polymerization method includes: mixing polymer monomers, lithium salts, organometallic complexes, and initiators in a mass ratio of 100:20-80:1-5:0.2-3 to form a polymer precursor solution, and initiating polymerization on the polymer precursor solution to obtain the polymer electrolyte; wherein the organometallic complex is dissolved in the polymer precursor solution.

[0024] Preferably, in the solution casting method, the polymer solution further includes one or more of the following: a film-forming agent, a plasticizer, and a filler; the mass ratio of the film-forming agent to the polymer matrix is ​​3:100-10:100; the mass ratio of the plasticizer to the polymer matrix is ​​15:100-40:100; and the mass ratio of the filler to the polymer matrix is ​​1:100-60:100.

[0025] In the in-situ polymerization method, the polymer precursor solution further includes one or more of the following: a film-forming agent, a plasticizer, and a filler; the film-forming agent accounts for 1%-5% of the polymer precursor solution by mass; the plasticizer accounts for 10%-40% of the polymer precursor solution by mass; and the filler accounts for 1%-5% of the polymer precursor solution by mass.

[0026] The film-forming agent includes one or more of FEC, LiDFOB, and lithium difluorophosphate;

[0027] The plasticizer includes one or more of succinic anhydride, tetraethylene glycol dimethyl ether, EC, VEC, VC, DMF, and DMAc;

[0028] The filler includes inorganic fillers and / or organic fillers; specifically, it includes active fillers and / or inert fillers, wherein the active filler is an inorganic solid electrolyte with ion-conducting capability, including one or more of perovskite type, NASICON type, garnet type, oxide glass and sulfide glass; the inert filler is a material without ion-conducting capability, including one or more of SiO2, ZrO2, Al2O3, TiO2, clay, metal-organic framework compound (MOF), and covalent organic framework (COF).

[0029] Preferably, in the solution casting method, the solvent includes one or more of the following: nitrile solvents, amide solvents, sulfonate solvents, phosphate solvents, and sulfone solvents;

[0030] The process of drying the polymer solution to obtain the polymer electrolyte specifically includes:

[0031] The polymer solution is uniformly coated onto one or both sides of a support material and then dried and cured to obtain the polymer electrolyte; or...

[0032] The polymer solution is uniformly coated onto the surface of the coating substrate material and then dried and cured. The dried and cured polymer electrolyte is then separated from the coating substrate material to obtain the polymer electrolyte.

[0033] Preferably, in the in-situ polymerization method, the polymer monomers include ethylene oxide, propylene oxide, 1,3-dioxane, vinylidene fluoride, vinylidene difluoride, vinylidene chloride, vinylene carbonate, ethylene ethylene carbonate, 1,3-propanesulfonate lactone, methyl methacrylate, ethyl acrylate, 1,6-hexanediol diacrylate, 2,2,2-trifluoroethyl acrylate, butyl acrylate, acrylic acid, 2,2,3,4,4,4-butyl hexafluoroacrylate, 2, 2,3,3,3-Pentafluoropropyl acrylate, acrylic acid, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, dodecafluoroheptyl acrylate, N,N'-methylenebisacrylamide, pentaerythritol glycidyl ether, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, methyl vinyl sulfone, vinyltrimethoxysilane, diethyl vinylphosphonate, acrylonitrile, polyethylene glycol monomethyl ether acrylate, and any one or more oligomers of the above components;

[0034] The process of initiating polymerization of the polymer precursor solution to obtain the polymer electrolyte specifically includes:

[0035] The polymer precursor solution is uniformly coated onto one or both sides of a support material, and in-situ polymerization is initiated by light and / or heat to obtain the polymer electrolyte; or...

[0036] The polymer precursor solution is uniformly coated onto the surface of the coating substrate material, and in-situ polymerization is initiated by light and / or heat. The polymer electrolyte is then separated from the coating substrate material to obtain the polymer electrolyte.

[0037] Thirdly, embodiments of the present invention provide an energy storage device comprising the polymer electrolyte containing a soluble organometallic complex as described in the first aspect above, or the polymer electrolyte containing a soluble organometallic complex prepared by the preparation method described in the second aspect above.

[0038] Preferably, the energy storage device includes: a lithium battery, a cell, or a battery pack.

[0039] This invention provides a polymer electrolyte containing a soluble organometallic complex, exhibiting excellent electrochemical performance and interfacial stability. By uniformly dispersing the soluble organometallic complex with surface-active sites at the molecular level within a polymer matrix, the problems of easy agglomeration, uneven dispersion, and poor interfacial contact inherent in traditional inorganic fillers in polymer electrolytes are effectively avoided. Furthermore, the Lewis acid-base interaction efficiency between the organometallic complex, polymer segments, and lithium salt is significantly improved. Specifically, the metal central ion in the organometallic complex acts as a Lewis acid, coordinating with Lewis basic groups such as ether radicals in the polymer segments or lithium salt anions. This regulates lithium ion transport, promotes the decomposition of lithium salt anions, and forms a stable interfacial film at the electrode interface, effectively suppressing side reactions. Thanks to this mechanism, the polymer electrolyte of this invention achieves a high ionic conductivity (~0.1 mS·cm). -1 The wide voltage window (>4.5V) significantly improves the solid-solid interface contact between the polymer electrolyte and the electrode, enhancing the thermal and electrochemical stability of the electrolyte, thereby improving the cycle performance and lifespan of the solid-state battery. Furthermore, by controlling the mass percentage of organometallic complexes in the polymer matrix (3%-10%), their efficient role in the polymer electrolyte system is achieved, further ensuring the optimization of the polymer electrolyte's performance. Attached Figure Description

[0040] Figure 1a The ionic conductivity comparison curves of Examples 1-3 and Comparative Example 1 of the present invention are shown.

[0041] Figure 1b The electrochemical impedance spectroscopy and ion transport number determination curves are for Comparative Example 1 of this invention.

[0042] Figure 1c The electrochemical impedance spectroscopy and ion transport number measurement curves are shown in Example 2 of this invention;

[0043] Figure 1d This refers to the electrochemical window of Examples 1-3 and Comparative Example 1 of the present invention;

[0044] Figure 1e The mechanical strength performance test curves of Examples 1-3 and Comparative Example 1 of the present invention are shown.

[0045] Figure 1f The X-ray diffraction (XRD) curves of Embodiment 2, Comparative Example 1, and PE membrane of the present invention are shown below.

[0046] Figure 1g The infrared spectral test results are for Examples 1-3 and the aluminum acetylacetone additive of the present invention;

[0047] Figure 1hThis is one of the infrared spectral test results of Examples 1-3 and Comparative Example 1 of the present invention;

[0048] Figure 1i This is the second of the infrared spectral test results of Examples 1-3 and Comparative Example 1 of the present invention;

[0049] Figure 2 The scanning electron microscope (SEM) morphology of lithium metal on the electrode of the Li|Li symmetric battery assembled in Example 2 of the present invention after 50 cycles.

[0050] Figure 2a Color images of the lithium anode in the Li|Li symmetric battery assembled in Example 2 after 50 cycles;

[0051] Figure 2b SEM morphology characterization of lithium metal on the electrode of the Li|Li symmetric battery assembled in Comparative Example 1 of this invention after 50 cycles.

[0052] Figure 2c The constant current charge-discharge test curves of the assembled Li|Li symmetric battery are shown in Embodiment 2 and Comparative Example 1 of the present invention.

[0053] Figure 2d The image shows the X-ray photoelectron spectroscopy (XPS) spectra of lithium metal after cycling of the Li|Li symmetric battery assembled in Comparative Example 1 of this invention.

[0054] Figure 2e The image shows the X-ray photoelectron spectroscopy (XPS) spectra of lithium metal after cycling of the Li|Li symmetric battery assembled in Embodiment 2 of the present invention.

[0055] Figure 2f The Tafel curves are those of Embodiments 1-3 and Comparative Example 1 of the present invention;

[0056] Figure 2g The AC impedance test results (without cycling) of the Li|Li symmetric cells assembled in Examples 1-3 and Comparative Example 1 of this invention;

[0057] Figure 2h EIS curves of the Li|Li symmetric cells assembled in Example 2 and Comparative Example 1 of the present invention after cycling for 50 cycles at different test temperatures, and Rct and RSEI impedance values ​​at each temperature obtained by fitting.

[0058] Figure 3a The results of rate performance tests were conducted on Li / LFP assembled in Example 2 and Comparative Example 1 of this invention, respectively.

[0059] Figure 3b The voltage-capacity curves of Embodiment 2 and Comparative Example 1 of the present invention at various rates of 0.1C, 0.2C, 0.5C, 1C, and 2C are shown.

[0060] Figure 3c The results of cycling performance tests were performed on Li / LFP assembled in Example 2 and Comparative Example 1 of this invention, respectively.

[0061] Figure 3d The results of charge-discharge cycle tests conducted at 60°C and 2C rate on the polymer electrolyte assembled batteries of Example 2 and Comparative Example 1 of this invention.

[0062] Figure 3e The results of charge-discharge cycle tests conducted at 30°C and 0.2C on the polymer electrolyte assembled batteries of Example 2 and Comparative Example 1 of this invention.

[0063] Figure 4a The ionic conductivity comparison curves for Example 4 and Comparative Example 2 of this invention are shown.

[0064] Figure 4b This refers to the electrochemical window of Example 4 and Comparative Example 2 of the present invention;

[0065] Figure 4c The electrochemical impedance spectroscopy and ion transport number measurement curves are for Comparative Example 2 of this invention;

[0066] Figure 4d The electrochemical impedance spectroscopy and ion transport number measurement curves are shown in Example 4 of this invention;

[0067] Figure 5a The Li|Li symmetric cell of Example 4 and Comparative Example 2 of this invention was tested at 30°C and 0.1 mA cm⁻¹. -2 Cyclic performance test curves at current density;

[0068] Figure 5b The Li|Li symmetric cell of Example 4 and Comparative Example 2 of this invention was tested at 30°C and 0.1 mA cm⁻¹. -2 -5mA cm -2 Cyclic performance test curves under current density conditions;

[0069] Figure 5c The cycling performance of the Li|lithium iron phosphate battery assembled with polymer electrolyte in Example 4 and Comparative Example 2 of this invention at 0.5C at 30°C;

[0070] Figure 5d The results of charge-discharge cycle tests at 30°C and 2C rate are for the polymer electrolyte assembled batteries of Example 4 and Comparative Example 2 of this invention.

[0071] Figure 6a These are the ionic conductivity comparison curves for Examples 2, 5, and 6 of the present invention and Comparative Example 1;

[0072] Figure 6b The results of linear sweep voltammetry (LSV) tests on the polymer electrolytes of Examples 2, 5, 6 and Comparative Example 1 of this invention are shown.

[0073] Figure 6c The results are the cycle performance test results of the polymer electrolyte assembled Li|Li symmetric batteries in Examples 2, 5, 6 and Comparative Example 1 of this invention;

[0074] Figure 7a These are the ionic conductivity comparison curves for Examples 2, 11, and Comparative Examples 1, 3, and 4 of the present invention;

[0075] Figure 7b The electrochemical windows of Examples 2, 11, 1, 3, and 4 of this invention are shown.

[0076] Figure 7c The curves show the comparison of the cycle performance of Comparative Example 1 and Comparative Example 3 of this invention.

[0077] Figure 7d This is a SEM image of the nano-sized LATP material used in this invention;

[0078] Figure 7e is a SEM image of the nano-sized LATP material after incorporation with electrolyte.

[0079] Figure 7f is a magnified view of a portion of Figure 7e. Detailed Implementation

[0080] This invention provides a polymer electrolyte containing a soluble organometallic complex, its preparation method, and its application.

[0081] In the embodiments of the present invention, if there are specific experimental steps or conditions that are not described in detail, the conventional experimental operation steps and conditions recorded in the literature in this field can be followed; if the manufacturers of the reagents or instruments used are not specified, they are all conventional reagents and instruments that can be obtained commercially.

[0082] To facilitate a better understanding of the present invention, some technical terms will be explained below.

[0083] "Organometallic complexes" refer to complexes formed by coordination bonds between organic ligands (organic compound molecules, organic acid radicals and organic groups) and a central ion or atom (which is a metal), forming stable complexes or chelates.

[0084] "Soluble organometallic complexes" refer to organometallic complexes that can dissolve / dissociate in polymer electrolytes, or the two can be dispersed and miscible, meaning that the organometallic complexes and the components of the polymer electrolyte form a molecular-level mixture.

[0085] "Active site" refers to a Lewis acid-base site. For example, the metal ions in a metal complex are positively charged and belong to Lewis acid sites, which can interact with the negatively charged Lewis bases in the polymer electrolyte.

[0086] "Support material" refers to substrate materials such as lithium-ion battery separators and non-woven porous membranes, preferably porous skeletons with a large number of interconnected pores that can be filled with polymers.

[0087] "Base film" refers to a thin film material with a thickness of micrometers that blocks electron transfer between the positive and negative electrodes, including lithium-ion battery separators made of materials such as polyethylene (PE) and polypropylene (PP).

[0088] "Porous membrane" refers to a membrane material with high porosity (greater than or equal to 50%) and interconnected internal pore structures. Preferably, it is a porous membrane with a thickness of 3-100 μm, a porosity of 50%-90%, and a pore size of 0.001-100 μm, wherein the pores include micropores, mesopores, and macropores, and the pore structure includes isolated pores and interconnected pores.

[0089] "Coating substrate" refers to materials that are not dissolved by polymer solutions or polymers, such as glass plates, petri dishes, polytetrafluoroethylene (PTFE) sheets or molds, and release paper.

[0090] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0091] First, embodiments of the present invention provide a polymer electrolyte containing a soluble organometallic complex, comprising: a polymer matrix, a lithium salt, and an organometallic complex.

[0092] In this process, the organometallic complex is uniformly distributed in the polymer matrix, forming a molecular-level mixture; the mass ratio of the organometallic complex to the polymer matrix is ​​3:100-10:100.

[0093] Organometallic complexes have active sites on their surface. These active sites act as Lewis acids and interact with polymer segments in the polymer matrix or anions in lithium salts, which act as Lewis bases, to form coordination structures.

[0094] Organometallic complexes include one or more of the following: acetylacetone complexes, isopropanol complexes, and ethoxy compounds.

[0095] The polymer matrix includes one or more of the following: polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), polyvinylidene chloride (PVDC), poly(polyethylene glycol monomethyl ether) (P(PEGMEA)), polyaramid, polyimide, polyvinylidene fluoride, polytetrafluoroethylene, or single-ion conductor polymer electrolytes (SICPEs). Specifically, the single-ion conductor polymer electrolyte may include one or more of the following: poly(1,4-phenylene ether sulfone)-lithium, polysulfone-lithium PSF-Li, hexafluoropolysulfone-lithium 6FPSF-Li, succinate (SN) plasticized ethylene carbonate (VEC), and 3-sulfonyltrifluoromethanesulfonylimide propyl lithium methacrylate (MASTFSILi) copolymer single-ion polymer conductors.

[0096] The lithium salt includes one or more of inorganic lithium salts or organic lithium salts; the lithium salt is preferably a lithium salt containing a sulfonyl group and / or a carbonyl group; more preferably, the lithium salt specifically includes one or more of lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate, and lithium perchlorate; the mass ratio of lithium salt to polymer matrix is ​​30:100-100:100.

[0097] The polymer matrix material of this invention has negatively charged groups, thus enabling it to interact with the reactive sites of organometallic complexes, i.e., the metal central ions of the organometallic complexes. In this invention, the surface of the organometallic complex has a large number of active sites and can be uniformly mixed with the polymer matrix. It should be noted that this "uniform mixing" is not a simple physical dispersion, but rather a process of dissolving the organometallic complex in a solvent or polymer monomer, followed by drying and curing or in-situ polymerization, to form a molecular-level mixed system with the polymer matrix, resulting in a polymer electrolyte. During the drying and curing or in-situ polymerization process, no solid-phase separation occurs; therefore, the organometallic complex of this invention can be homogeneously distributed in the polymer electrolyte. That is, from a macroscopic perspective, the organometallic complex is dissolved in the polymer electrolyte, forming a polymer electrolyte containing soluble organometallic complexes.

[0098] This invention does not impose excessive restrictions on the polymer matrix material, as long as it can provide negatively charged groups to ensure interaction with soluble organometallic complexes. For example, the metal central ion in the organometallic complex undergoes Lewis acid-base interactions with negatively charged groups (such as etheroxy groups) in the polymer segments. Therefore, the improvements of this invention have high versatility and are applicable to various types of polymer matrix materials. Furthermore, the polymer matrix material segments can also incorporate materials containing strong electron-withdrawing groups, such as copolyboranes, copolysiloxanes, and copolyamides, through cross-linking copolymerization. These materials can also effectively regulate interfacial properties, promote lithium salt dissociation, and improve ionic conductivity by adsorbing anions.

[0099] The lithium salt in the polymer matrix is ​​defined as 30%-100% by mass, and can be any value within this range, including 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%, but is not limited thereto. The lithium salt of this invention can provide anions that react with the metal ions in the organometallic complex via Lewis acid-base interactions. Lithium salts containing sulfonyl or carbonyl groups are more preferred. Because lithium salts containing sulfonyl or carbonyl groups possess oxygen that can effectively coordinate with metal ions, they are more conducive to strong Lewis acid-base interactions with the metal ions in the organometallic complex, thereby effectively promoting the decomposition of anions in the lithium salt and facilitating the formation of an SEI film at the interface between the polymer electrolyte and the positive and negative electrodes, effectively suppressing interfacial side reactions.

[0100] The organometallic complex of this invention dissolves in the polymer electrolyte, forming a molecular-level mixture with the polymer electrolyte matrix and lithium salt, thus creating a homogeneous mixture. This effectively avoids the problem of poor contact performance caused by reduced interfacial contact area between inorganic and organic components due to the agglomeration of inorganic fillers. Furthermore, the organometallic complex has numerous active sites on its surface, enabling Lewis acid-base interactions with the polymer electrolyte matrix and / or lithium salt. This improves ionic conductivity, achieves a high voltage window, and effectively suppresses interfacial side reactions. It also effectively avoids the safety hazards and mechanical property degradation associated with plasticizers, ensuring excellent cycle performance and significantly improving cycle life when the polymer electrolyte is used in solid-state batteries.

[0101] The organometallic complexes of the present invention preferably include acetylacetone complexes; acetylacetone complexes refer to metal complexes of acetylacetone, and may specifically include, but are not limited to, one or more of aluminum acetylacetone, nickel acetylacetone, copper acetylacetone, zinc acetylacetone, and zirconium acetylacetone, and are more preferably one or more of aluminum acetylacetone, zinc acetylacetone, and zirconium acetylacetone. Further, it is more preferably an acetylacetone complex containing a carbonyl group. In organometallic complexes containing a carbonyl group, the carbonyl group coordinates with the metal central ion. For example, in aluminum acetylacetone, the two carbonyl groups in the acetylacetone ligand can coordinate with the aluminum ion, the metal central ion, and the strong electron-withdrawing property of the carbonyl group further enhances the Lewis acidity of the metal central ion, thereby efficiently interacting with the negatively charged groups in the polymer matrix or the anions of lithium salts.

[0102] One reason for favoring acetylacetone complexes is their excellent solubility in organic solvents, allowing for uniform distribution within the polymer electrolyte. This eliminates the interfacial contact issues caused by phase separation between the polymer electrolyte matrix and the acetylacetone complex. In a specific example of this invention, the acetylacetone complex is uniformly distributed within the polymer electrolyte. The localized decomposition of the acetylacetone complex creates numerous positive and negatively charged sites within the polymer electrolyte, resulting in stronger interactions between the acetylacetone complex, polymer segments, and lithium salt. This effectively regulates lithium-ion transport, achieving higher ionic conductivity.

[0103] Another reason for favoring acetylacetone complexes is that they promote anion decomposition and film formation, thereby inhibiting interfacial side reactions. Using acetylacetone complex additives promotes film formation without introducing liquid phase components and ensures the stability of the interfacial SEI film. For example, acetylacetone complexes can promote the reduction and decomposition of anions of fluorinated lithium salts (such as LiPF6, LiTFSI, LiFSSI, etc.) on the electrode surface during electrochemical processes, generating inorganic substances such as LiF, forming a fluorine-rich SEI film. These fluorine-rich SEI films possess high mechanical strength and chemical stability, effectively passivating the electrode surface, regulating lithium deposition, and inhibiting electrolyte corrosion, thereby improving the battery's electrochemical performance and cycle life. Therefore, acetylacetone complexes have a superior effect in promoting anion-stabilized film formation. By inducing the formation of a fluorine-rich interfacial film, they prevent side reactions between the polymer electrolyte and electrode materials, especially the lithium metal anode active material, thus achieving a high voltage window.

[0104] The acetylacetone complex used in the polymer electrolyte of this invention can strongly interact with various polymer electrolyte matrices and lithium salts, exhibiting very high versatility. Due to the local decomposition of the acetylacetone complex, it can effectively promote the decomposition of lithium salt anions into a film and can coordinate with negatively charged sites on the polymer to regulate polymer chain segments. By adding the acetylacetone complex, this invention not only improves ionic conductivity, achieves a high voltage window, and effectively suppresses interfacial side reactions, but also effectively improves the mechanical properties of the polymer electrolyte. Its mechanical strength and elongation are significantly enhanced, resulting in excellent electrochemical performance, such as cycling performance, when used in solid-state batteries. Furthermore, due to its higher safety performance, it can greatly improve battery cycle life, achieving stable cycling of over 1000 cycles or stable operation at room temperature.

[0105] As described above, the organometallic complexes of the present invention may also be one or more of isopropanol complexes and ethoxy compounds. Isopropanol complexes include aluminum isopropoxide, and ethoxy compounds include aluminum triethoxy.

[0106] The mass ratio of the organometallic complex to the polymer matrix specified in the present invention is 3:100-10:100, and can be any value within the above range, such as 3.0%, 3.5%, 4%, 4.5%, 5.0%, 5.5%, 6%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, but is not limited thereto.

[0107] Maintaining the mass percentage of organometallic complexes between 3% and 10% is based on a comprehensive consideration of performance optimization and material stability. This ratio aims to improve electrolyte performance while avoiding the potential negative impacts of excessive addition.

[0108] If the content of organometallic complexes is too low, it may prevent sufficient Lewis acid-base interactions with polymer segments or lithium salt anions, making it difficult to regulate lithium-ion transport and suppress side reactions. If the content of organometallic complexes is too high, it will become an obstacle in the lithium-ion transport pathway in the polymer phase, blocking lithium-ion transport and reducing lithium-ion conductivity.

[0109] An appropriate amount of organometallic complex can undergo Lewis acid-base interactions with negatively charged groups (such as ether radicals) in polymer segments and lithium salt anions, forming channels that facilitate lithium ion migration, improving ionic conductivity, effectively regulating lithium ion transport, and promoting the formation of a sufficiently stable SEI film. In this invention, the mass percentage of the organometallic complex is more preferably 3%-5%.

[0110] The polymer electrolyte of the present invention further includes a supporting material; the supporting material includes one or more of the following: a base film, nonwoven fabric, glass fiber, and fiber composite material; preferably, the supporting material is a porous supporting material, which can improve the adhesion amount; the porous supporting material can be one or more of PE, PP, nonwoven fabric, and polyimide. More preferably, the supporting material is a porous base film, which can effectively isolate electron transport and has a better effect.

[0111] The porosity of the support material of this invention is 50%-90%, and can be any value within the above range, such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., but is not limited thereto. Using a porous support material facilitates the dispersion of the polymer electrolyte, which adheres to the inner and outer surfaces of the porous substrate. By filling the porous structure with the polymer electrolyte of this invention, more ion transport channels can be formed, which is beneficial for lithium-ion transport. The support material serves to support the polymer electrolyte. When the support material is a membrane, especially a porous membrane, it can act as a framework to provide considerable mechanical properties, compensating for the weak mechanical properties of the polymer electrolyte material, and providing interconnected pore structures for the polymer electrolyte material to fill and form an interconnected lithium-ion transport network. For example, it ensures sufficient effective adsorption of the polymer electrolyte and facilitates in-situ polymerization of the polymer precursor solution, thus making it suitable for solid-state batteries, in-situ solid-state batteries, and all-solid-state batteries.

[0112] Polymer electrolytes may also include film-forming agents.

[0113] The film-forming agent includes one or more of fluoroethylene carbonate (FEC), lithium difluorooxalate borate (LiDFOB), and lithium difluorophosphate; the mass ratio of the film-forming agent to the polymer matrix is ​​3:100-10:100, and can be any value within the above range, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%, but is not limited thereto.

[0114] Polymer electrolytes may also include plasticizers.

[0115] The plasticizer includes one or more of succinic anhydride, tetraethylene glycol dimethyl ether, ethylene carbonate (EC), ethylene ethylene carbonate (VEC), ethylene ethylene carbonate (VC), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc); the mass ratio of the plasticizer to the polymer matrix is ​​15:100-40:100, and can be any value within the above range, such as 15%, 16%, 17%, 18%, 19%, 20%, 30%, 40%, but is not limited thereto.

[0116] This invention introduces a film-forming agent, such as FEC, into the polymer electrolyte, which can spontaneously decompose to construct a high-performance SEI, thereby facilitating the formation of the interfacial SEI film. The use of a plasticizer in this invention also helps to improve the voltage window and ionic conductivity of the polymer electrolyte. The introduction of organometallic complexes into the polymer electrolyte of this invention, due to the interaction between the organometallic complexes and polymer segments and lithium salts, can overcome the decrease in mechanical strength caused by the introduction of small amounts of film-forming agents and plasticizers, and prevent interfacial side reactions. However, given that the introduction of film-forming agents and / or plasticizers increases the liquid phase composition of the polymer electrolyte or leads to increased costs, it is necessary to control the addition amount of the above two components within the above range, and preferably control the sum of the addition amount of the two components to below 50% (based on the polymer matrix), thereby effectively preventing excessive degradation of the mechanical strength of the polymer electrolyte and interfacial side reactions with the electrode due to the introduction of the above components.

[0117] Polymer electrolytes may also include fillers.

[0118] The filler includes inorganic fillers and / or organic fillers; specifically, it includes active fillers and / or inert fillers. The active filler is an inorganic solid electrolyte with ion-conducting capabilities, including one or more of perovskite, NASICON, garnet, oxide glass, and sulfide glass. The inert filler is a material without ion-conducting capabilities, including one or more of silicon dioxide (SiO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), titanium oxide (TiO2), clay, metal-organic frameworks (MOFs), and covalent organic frameworks (COFs). The mass ratio of filler to polymer matrix is ​​1:100-60:100, and can be any value within the above range, such as 1%, 5%, 10%, 20%, 30%, 40%, 50%, and 60%, but is not limited thereto.

[0119] This invention introduces soluble organometallic complexes into the polymer electrolyte, which have sufficient contact area and interaction with the polymer matrix and lithium salt. This effectively controls the solid-solid interface contact problem caused by a small amount of inorganic and / or organic fillers. By controlling the content of inorganic and / or organic fillers to be below 60% relative to the polymer matrix, the excessive degradation of the interface performance of the polymer electrolyte due to the introduction of the above components can be effectively controlled.

[0120] In summary, the polymer electrolyte containing soluble organometallic complexes proposed in this invention, by introducing soluble organometallic complex additives into the polymer electrolyte, can increase and improve the solid-solid contact area between the polymer electrolyte and the additives, thereby achieving high ionic conductivity (~0.1 mS / cm). -1Based on the high voltage window (>4.5V), it effectively suppresses the occurrence of interfacial side reactions between the electrolyte and the electrode, improves the mechanical and safety performance of the polymer electrolyte, improves the cycle performance of the solid-state battery, and increases the cycle life, thereby ensuring the use requirements of the solid-state battery.

[0121] The present invention also provides a method for preparing the polymer electrolyte containing the above-mentioned soluble organometallic complex.

[0122] One feasible preparation method is solution casting. In this method, a solvent needs to be added to ensure thorough mixing of the polymer matrix material, lithium salt, and organometallic complex, especially ensuring that the organometallic complex dissolves in the organic solvent.

[0123] Specifically, the solution casting method includes: uniformly mixing a polymer matrix, lithium salt, organometallic complex, and solvent in a mass ratio of 100:30-100:3-10:1000-2000 to form a polymer solution, and drying the polymer solution to obtain a polymer electrolyte; wherein the organometallic complex is dissolved in the polymer solution. The solvent includes one or more of the following: nitrile solvents, amide solvents, sulfonate solvents, phosphate solvents, and sulfone solvents.

[0124] Specific methods for drying the polymer solution can be as follows: uniformly coating the polymer solution onto one or both sides of a support material and then drying and curing it to obtain a polymer electrolyte; or uniformly coating the polymer solution onto the surface of a coating substrate material and then drying and curing it, and then separating the dried and cured polymer electrolyte from the coating substrate material to obtain the polymer electrolyte. That is, the polymer electrolyte of the present invention may or may not contain a support material, depending on the application requirements, and a corresponding drying method is selected for preparation.

[0125] In the solution casting method, the polymer solution may also include one or more of the following: film-forming agent, plasticizer, and filler; the mass ratio of film-forming agent to polymer matrix is ​​3:100-10:100; the mass ratio of plasticizer to polymer matrix is ​​15:100-40:100; and the mass ratio of filler to polymer matrix is ​​1:100-60:100.

[0126] The film-forming agents, plasticizers, and fillers are the same as those described in the above description of polymer electrolyte products containing soluble organometallic complexes, and will not be repeated here.

[0127] Another feasible preparation method is in-situ polymerization.

[0128] The in-situ polymerization method includes: mixing polymer monomers, lithium salts, organometallic complexes, and initiators in a mass ratio of 100:20-80:1-5:0.2-3 to form a polymer precursor solution, and initiating polymerization on the polymer precursor solution to obtain a polymer electrolyte; wherein the organometallic complex is dissolved in the polymer precursor solution.

[0129] In the in-situ polymerization method, the polymer monomers include any one or more of the following: ethylene oxide, propylene oxide, 1,3-dioxane, vinylidene fluoride, vinylidene chloride, vinylene carbonate, ethylene ethylene carbonate, 1,3-propanesulfonate lactone, methyl methacrylate, ethyl acrylate, 1,6-hexanediol diacrylate, 2,2,2-trifluoroethyl acrylate, butyl acrylate, acrylic acid, 2,2,3,4,4,4-hexafluoroacrylate butyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, acrylic acid, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, dodecafluoroheptyl acrylate, N,N'-methylenebisacrylamide, pentaerythritol glycidyl ether, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, methyl vinyl sulfone, vinyltrimethoxysilane, diethyl vinylphosphonate, acrylonitrile, polyethylene glycol monomethyl ether acrylate, and oligomers of the above components.

[0130] The method for initiating polymerization of a polymer precursor solution may specifically include: uniformly coating the polymer precursor solution onto one or both sides of a support material, and initiating in-situ polymerization by light and / or heat to obtain a polymer electrolyte; or, uniformly coating the polymer precursor solution onto the surface of a coating substrate material, initiating in-situ polymerization by light and / or heat, and separating the polymerized polymer electrolyte from the coating substrate material to obtain the polymer electrolyte. That is, the polymer electrolyte of the present invention may or may not contain a support material, depending on the application requirements, and the appropriate preparation method is selected.

[0131] In the in-situ polymerization method, the polymer precursor solution may also include one or more of the following: film-forming agent, plasticizer, and filler; the mass percentage of film-forming agent in the polymer precursor solution is 1%-5%; the mass percentage of plasticizer in the polymer precursor solution is 10%-40%; and the mass percentage of filler in the polymer precursor solution is 1%-5%.

[0132] The film-forming agents, plasticizers, and fillers are the same as those described in the above description of polymer electrolyte products containing soluble organometallic complexes, and will not be repeated here.

[0133] In this method, organometallic complexes that are soluble in the polymer monomer are preferably selected. When the selected organometallic complex is poorly soluble in the monomer, a solvent needs to be added, specifically an organic solvent, including one or more of nitrile solvents, amide solvents, sulfonate solvents, phosphate solvents, and sulfone solvents.

[0134] In-situ polymerization, by polymerizing organometallic complex additives, lithium salts, and monomers in situ, forms an in-situ polymerized solid electrolyte. This method offers excellent dispersibility and solid-solid contact. In in-situ polymerization, the interaction between the organometallic complex and the polymer monomer is stronger, leading to earlier polymerization. Precursor solution in-situ polymerization enables better contact between the polymer matrix material and the organometallic complex additive, effectively solving the solid-solid interface contact problem within the polymer electrolyte and forming a good solid-solid contact, significantly improving lithium-ion transport performance. Furthermore, organometallic complexes, especially acetylacetone complexes, can effectively promote anion decomposition and film formation, thereby effectively preventing electrochemical reactions between the polymer electrolyte and electrode materials, especially the lithium metal anode interface, thus improving battery cycle performance and energy density.

[0135] The coating substrate materials mentioned in the two methods above include one or more of the following: glass plate, petri dish, polytetrafluoroethylene mold, polytetrafluoroethylene plate, release paper, and PET release film. When using the coating substrate material in this invention, a flat carrier can be provided for the polymer precursor, facilitating peeling after film formation. This invention is suitable for solid-state batteries, in-situ solid-state batteries, and all-solid-state batteries.

[0136] The mixing methods mentioned above can be employed in various ways, such as stirring, shaking, or mixing in a mixer truck, but are not limited to these. For stirring, mechanical stirring or manual stirring may be used, and the mixing time should be longer than 12 hours, with the goal of ensuring that the substances are mixed evenly and that the organometallic complex is dissolved.

[0137] The solution coating methods mentioned in the two methods above can include, but are not limited to, various methods such as dip coating, blade coating, air knife coating, and roller coating.

[0138] The polymer electrolyte containing soluble organometallic complexes obtained by this invention can be used as an electrolyte for secondary batteries, and can be applied in lithium batteries, cells, battery packs, lithium battery modules or lithium battery components. It can be widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields, and also has good application prospects in large-scale energy storage systems.

[0139] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0140] In the following embodiments, the porous membrane used is a lithium battery separator made of polyethylene (PE) with a porosity of ≥50%.

[0141] The porosity was determined using the following method:

[0142] According to the method in GB / T 36363-2018, three diaphragm pieces are cut longitudinally from the membrane roll at 150mm intervals. If the diaphragm width is >100mm, the sample size is 100mm x 100mm; if the diaphragm width is <100mm, the sample size is 100mm x diaphragm width. The length, width, and thickness of the diaphragm are measured according to the provisions of GB / T6673-2001 and GB / T6672-2001, respectively. The membrane density ρ is then calculated, and the porosity is the relative difference between ρ and the density ρ0 of the diaphragm raw material (ρ0-ρ) / ρ0×100%.

[0143] Example 1

[0144] This example uses the solution casting method.

[0145] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), aluminum acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.03:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0146] Example 2

[0147] This example uses the solution casting method.

[0148] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), aluminum acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0149] Example 3

[0150] This example uses the solution casting method.

[0151] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), aluminum acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.1:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0152] Example 4

[0153] This example uses the solution casting method.

[0154] Polyvinylidene fluoride (PVDF), lithium bis(fluorosulfonyl)imide (LiFSI), aluminum acetylacetonate, and N,N-dimethylformamide (DMF) were mixed at 50°C for 12 h in a mass ratio of 1:1:0.05:13 to form a polymer solution. The solution was then directly coated onto a glass plate using a 1000-micron doctor blade and subsequently vacuum dried at 55°C for 24 h. After the polymer electrolyte was peeled off from the glass plate, the plate was cut and used for testing.

[0155] Example 5

[0156] This example uses the solution casting method.

[0157] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), zinc acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0158] Example 6

[0159] This example uses the solution casting method.

[0160] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), zirconium acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0161] Example 7

[0162] This example uses the solution casting method.

[0163] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), nickel acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0164] Example 8

[0165] This example uses the solution casting method.

[0166] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), copper acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0167] Example 9

[0168] This example uses the solution casting method.

[0169] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), aluminum isopropoxide, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0170] Example 10

[0171] This example uses the solution casting method.

[0172] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), aluminum ethoxylate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0173] Example 11

[0174] This example uses the solution casting method.

[0175] Polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFS I), aluminum acetylacetonate, and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.36:0.03:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0176] Example 12

[0177] This example uses in-situ polymerization.

[0178] A precursor solution was prepared by mixing monomers ethylene ethylene carbonate (VEC), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOB), butyl 2,2,3,4,4,4-hexafluoroacrylate (HFBA), N,N'-methylenebisacrylamide (MBA), aluminum acetylacetonate, and initiator phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO) in a mass ratio of 1:0.24:0.06:0.25:0.03:0.03:0.005. This precursor solution was then coated onto both sides of a porous PE membrane using a 20-micron wire rod. The membrane was subsequently irradiated with 365 nm UV light for 5–15 min to obtain a polymer electrolyte membrane, which was then cut and used for testing.

[0179] Comparative Example 1

[0180] This example uses the solution casting method.

[0181] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0182] Comparative Example 2

[0183] This example uses the solution casting method.

[0184] Polyvinylidene fluoride (PVDF), lithium bis(fluorosulfonyl)imide (LiFSI), and N,N-dimethylformamide (DMF) were mixed at a mass ratio of 1:1:13 at 50°C for 12 hours to form a polymer solution. The solution was then directly coated onto a glass plate using a 1000-micron doctor blade and subsequently vacuum dried at 55°C for 24 hours. After the polymer electrolyte was peeled off from the glass plate, the plate was cut into pieces for testing.

[0185] Comparative Example 3

[0186] This example uses the solution casting method.

[0187] Polyethylene oxide (PEO), succinate (SN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium titanium aluminum phosphate (LATP), and acetonitrile were mixed at room temperature for 12 h in a mass ratio of 1:0.27:0.36:0.05:15 to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70 °C for 24 h. After cutting, the membrane was used for testing.

[0188] Comparative Example 4

[0189] This example uses the solution casting method.

[0190] Polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and acetonitrile were mixed at a mass ratio of 1:0.36:15 at room temperature for 12 hours to form a polymer solution. The solution was then coated on both sides of a PE membrane using a 250-micron doctor blade and subsequently vacuum dried at 70°C for 24 hours. The membrane was then cut into pieces for testing.

[0191] Comparative Example 5

[0192] This example uses in-situ polymerization.

[0193] A precursor solution was prepared by mixing monomers ethylene ethylene carbonate (VEC), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOB), butyl 2,2,3,4,4,4-hexafluoroacrylate (HFBA), N,N'-methylenebisacrylamide (MBA), and initiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO) in a mass ratio of 1:0.24:0.06:0.25:0.03:0.005. This precursor solution was then coated onto both sides of the aforementioned porous PE-based membrane using a 20-micron wire rod. The membrane was subsequently irradiated with 365 nm ultraviolet light for 5-15 min to obtain a polymer electrolyte membrane, which was then cut and used for testing.

[0194] The above embodiments and comparative examples were tested:

[0195] (I) In order to characterize the modification effect of organometallic complexes and their regulation mechanism, the basic performance of PEO-based polymer electrolytes (Examples 1-3, Comparative Example 1) with different doses of aluminum acetylacetonate additives were characterized, including: ionic conductivity, ion transport number, electrochemical window, mechanical strength, X-ray diffraction, and infrared spectroscopy.

[0196] (1) Ionic conductivity test of polymer electrolyte:

[0197] ① Assembly of stainless steel | Stainless steel symmetrical battery: Stainless steel gaskets (area S) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. Its thickness L is tested before assembly. No electrolyte is required. The CR2032 button cell is assembled directly.

[0198] ② AC Impedance Testing: Using a Chenhua CHI650e electrochemical workstation and a variable-temperature battery oven, the AC impedance spectra of stainless steel / stainless steel batteries at open-circuit voltages were measured at 30℃, 40℃, 50℃, 60℃, and 70℃, with a frequency range of 1×10⁻⁶. 6 Hz-1Hz, amplitude 5mA.

[0199] ③ Ionic conductivity calculation: Read the resistance value Rb at the intersection of the EIS curve and the horizontal axis (Z' axis), and substitute it into the ionic conductivity calculation formula σ=L / (Rb·S) to obtain the ionic conductivity at each temperature.

[0200] (2) Ion transport number test of polymer electrolytes:

[0201] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and CR2032 coin cells are assembled directly.

[0202] ② Ion transport number test: The AC impedance spectrum of the Li|Li symmetric cell at 60℃ was tested using a Nova Autolab electrochemical workstation, with a frequency range of 1×10⁻⁶. 6 The frequency was 1 Hz - 1 Hz, with an amplitude of 5 mA. Then, a constant potential polarization test was performed. A polarization potential of V = 10 mV was applied to the battery, and the change of the battery current signal over time was recorded for 2 hours. Then, an AC impedance test was performed under the same conditions, resulting in two sets of EIS curves and one set of current-time curves.

[0203] ③ Ion transport number calculation: Read the impedance values ​​R0 and Rs at the intersection of the right side of the complete semicircle of the EIS curve before and after polarization and the horizontal axis. Read the current values ​​I0 and Is at the beginning and end of polarization. Substitute these values ​​into the ion transport number t. Li+ The calculation formula t Li+ The ion transport number is obtained by calculating (Is·(V-I0R0)) / (I0·(V-IsRs)). In this formula, V is the polarization voltage, which is a constant potential applied during the test, 10mV; I0 and Is are the current values ​​at the initial polarization moment and after the polarization steady state, respectively; R0 and Rs are the electrolyte interface resistances before and after polarization (obtained from the intersection of the right end of the high-frequency arc and the horizontal axis in the AC impedance spectrum).

[0204] (3) Electrochemical window testing of polymer electrolytes:

[0205] ① Assembly of Li|Stainless Steel Half-Cell: The negative electrode uses a lithium sheet (500μm thick), the positive electrode uses a stainless steel gasket, and the separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and the CR2032 coin cell is directly assembled.

[0206] ② Electrochemical window test: Using a Chenhua CHI 650e electrochemical workstation and a variable temperature battery oven, the LSV curve of the Li|stainless steel battery was tested. The voltage range was 3-7V, the scan rate was +1mV / s, and the change of current signal over time was recorded. The potential value at the point where the current begins to increase suddenly was taken as the electrochemical window of the electrolyte.

[0207] (4) Mechanical property testing of polymer electrolytes:

[0208] Using a universal mechanical testing instrument, a polymer electrolyte sample with a width of 1 cm and an effective length of 2 cm was installed and stretched at a speed of 20 mm / min until it broke. The stress and strain values ​​during this process were recorded by the testing instrument to obtain a stress-strain curve. The peak stress and maximum strain of the curve are the mechanical strength and elongation of the electrolyte, respectively.

[0209] (5) X-ray diffraction test of polymer electrolyte:

[0210] The prepared solid electrolyte membrane was tested using a Rigaku-9kW X-ray diffractometer at a scan rate of 10° / min and an angle range of 5°–40°, and the corresponding XRD curves were obtained.

[0211] (6) Infrared spectroscopy test:

[0212] Infrared spectroscopy was performed using the reflectance mode of a Thermo Fisher Scientific ATR IS50 FTIR meter, with a wavenumber range of 400-4000 cm⁻¹. -1 Infrared spectral curves were obtained, and peak spectra within a specific wavenumber range were analyzed.

[0213] Table 1 summarizes the test data of some basic properties of PEO-based polymer electrolytes under different amounts of aluminum acetylacetonate.

[0214]

[0215] The above tests can be used to compare the modification performance of different additives used in the PEO polymer electrolyte system in Examples 1-3 and Comparative Example 1.

[0216] In the polymeric electrolytes of Examples 1-3, the amounts of aluminum acetylacetone additive added relative to the polymeric electrolyte matrix were 3 wt%, 5 wt%, and 10 wt%, respectively, while Comparative Example 1 did not contain the acetylacetone additive. As shown in Table 1, the ionic conductivity of the polymeric electrolyte of Example 1 reached 4.22 × 10⁻⁶ at 30°C. -5 S / cm, reaching 8.43×10 at 40℃ - 5 S / cm, reaching 1.48×10 at 50℃ -4S / cm, reaching 2.22×10 at 60℃ -4 S / cm, reaching 3.08×10 at 70℃ -4 S / cm; The ionic conductivity of the polymer electrolyte in Example 2 reached 7.89 × 10⁻⁶ at 30°C. -5 S / cm, reaching 1.22×10 at 40℃ -4 S / cm, reaching 1.81×10 at 50℃ -4 S / cm, reaching 2.87×10 at 60℃ -4 S / cm, reaching 3.41×10 at 70℃ -4 S / cm; The ionic conductivity of the polymer electrolyte in Example 3 reached 2.40 × 10⁻⁶ at 30°C. -5 S / cm, reaching 4.90×10 at 40℃ -5 S / cm, reaching 9.57×10 at 50℃ -5 S / cm, reaching 1.49×10 at 60℃ -4 S / cm, reaching 2.21×10 at 70℃ -4 S / cm. Ionic conductivity test as follows: Figure 1a As shown, with a suitable amount of aluminum acetylacetonate, the ionic conductivity of the polymer electrolyte was significantly improved, approaching or exceeding 0.1 mS / cm. Overall, relative to the PEO polymer matrix, the ionic conductivity at different temperatures showed a trend of first increasing and then decreasing with increasing aluminum acetylacetonate content. When the aluminum acetylacetonate additive was 5 wt%, the polymer electrolyte exhibited the highest ionic conductivity at different temperatures, reaching 1.22 × 10⁻⁶ at 40℃. -4 The S / cm is one order of magnitude higher than that of other examples, and the ionic conductivity at a high temperature of 70°C can reach as high as 3.41 × 10⁻⁶. -4 S / cm.

[0217] The polymer electrolyte in Comparative Example 1, which does not contain aluminum acetylacetonate, exhibits an ionic conductivity of 3.04 × 10⁻⁶ at 30 °C. -5 S / cm, reaching 6.23×10 at 40℃. -5 S / cm, reaching 1.15×10 at 50℃ -4 S / cm, reaching 1.77×10 at 60℃ -4 S / cm, reaching 2.58×10 at 70℃ -4S / cm. It can be seen that when the amount of acetylacetone additive added is 3wt% and 5wt%, the ionic conductivity of the polymer electrolyte at various temperatures is significantly higher than that of the polymer electrolyte without added aluminum acetylacetone. While the ionic conductivity of the polymer electrolyte at various temperatures is lower than that of the polymer electrolyte without added aluminum acetylacetone when the amount of acetylacetone additive added is 10wt%, the difference is not significant. This indicates that when the content of aluminum acetylacetone additive added to the polymer electrolyte is within an appropriate range, it can ensure excellent ionic conductivity. Increasing the additive content hinders lithium ion transport in the polymer electrolyte, causing a decrease in ionic conductivity. Therefore, the content of aluminum acetylacetone additive needs to be limited to an appropriate range. Furthermore, it can be seen that when the amount of acetylacetone additive added is 10wt%, its ionic conductivity at 60℃ and 70℃ is still higher than 0.1 mS / cm. -1 The level remains relatively high.

[0218] like Figure 1b and Figure 1c As shown, the ion transport numbers of Comparative Example 1 and Example 2 are 0.2 and 0.45, respectively. This indicates that the addition of aluminum acetylacetonate to the polymer electrolyte can effectively increase the ion transport number, indicating that the additive can effectively anchor anions.

[0219] Figure 1d The electrochemical windows of different polymer electrolytes are shown. The electrochemical windows of the polymer electrolytes in Examples 1-3 reached 4.61V, 4.75V, and 4.72V, respectively, while that of Comparative Example 1 was only 4.42V. It can be seen that with the increase of the aluminum acetylacetonate additive content, the electrochemical window of the polymer electrolyte shows a trend of first increasing and then decreasing, but it is significantly higher than that of the polymer electrolyte without the additive. The electrochemical windows of the polymer electrolytes in Examples 2-3 all reached above 4.7V. This indicates that aluminum acetylacetonate, as an additive in polymer electrolytes, can significantly improve the high-voltage window of the polymer electrolyte, and the highest electrochemical window is achieved when the amount of aluminum acetylacetonate additive is 5wt%.

[0220] Figure 1eThe mechanical property test curves of the polymer electrolytic materials are shown. The mechanical strengths of the polymer electrolytes in Examples 1-3 reached 43.1 MPa, 59.9 MPa, and 85.5 MPa, respectively, and the elongation was 86.48%, 59.62%, and 48.41%, respectively. In contrast, the mechanical strength of Comparative Example 1 was only 36.7 MPa, and the elongation was only 36.78%. It can be seen that the polymer electrolytes in Examples 1-3 and Comparative Example 1 all contain 27% plasticizer relative to the polymer matrix. However, it can be seen that by adding aluminum acetylacetonate as an additive to the polymer electrolyte, the mechanical strength and elongation of the polymer electrolyte were significantly improved compared to the polymer electrolyte without this additive. This also indicates that the addition of aluminum acetylacetonate can effectively overcome the problem of decreased mechanical strength caused by the introduction of plasticizers. It can be seen that when the amount of aluminum acetylacetonate additive is 5 wt%, it has the best overall mechanical properties, ensuring a significant improvement in both mechanical strength and elongation. Therefore, with the addition of aluminum acetylacetonate, the mechanical strength of the polymer electrolyte is significantly improved. This is because aluminum acetylacetonate can act as a crosslinking agent in the polymer electrolyte, thereby improving the mechanical properties of the polymer electrolyte.

[0221] Figure 1f The XRD tests of Example 2, Comparative Example 1, and the PE membrane show that the crystallinity of the PEO matrix in Example 2 decreased significantly, indicating that the polymer has higher segment activity, which helps to improve the migration behavior of lithium ions.

[0222] Figure 1g -i shows the infrared spectral tests of Examples 1-3 and Comparative Example 1, as well as the aluminum acetylacetonate additive, to illustrate the modification principle of PEO segments by aluminum acetylacetonate. Figure 1g The weakening of the vibrational peak corresponding to the Al-ligand indicates that the aluminum acetylacetone complex can undergo partial decomplexation in the PEO matrix, thereby exposing more Lewis acidic sites to interact with PEO segments and anions. Figure 1h The peak shift and relative intensity change of the PEO segment also indicate the interaction between aluminum acetylacetonate and the PEO segment after addition, and are consistent with the XRD results. Figure 1i An additional peak signal appeared in the sulfonyl vibration peak of the TFSI, indicating that it coordinated with other positively charged sites besides lithium ions. Since the amount of aluminum acetylacetonate added was the only variable, it can be concluded that the aluminum sites in the partially decomplexed aluminum acetylacetonate coordinated with the sulfonyl group, thus resulting in the peak signal at 1340 cm⁻¹. -1 A new peak appeared nearby, which is consistent with the ion transference number results, indicating that the aluminum acetylacetone additive has an anchoring effect on the anions in the lithium salt.

[0223] (II) In order to illustrate the effect of aluminum acetylacetone additive on the lithium metal anode side, a series of basic performance characterizations were carried out on PEO-based polymer electrolytes (Examples 1-3, Comparative Example 1) with different amounts of aluminum acetylacetone additive, including: constant current Li|Li symmetric cell cycle test, scanning electron microscopy test, X-ray photoelectron spectroscopy, Tafel curve, AC impedance test, and variable temperature AC impedance test.

[0224] (1) Constant current Li|Li symmetric cell cycle test includes:

[0225] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and CR2032 coin cells are assembled directly.

[0226] ② Constant current charge-discharge cycle: Using the LAND battery test channel at 0.1mA cm -2 The battery was charged and discharged at the current density for 1 hour each, and the charging and discharging were repeated continuously. The battery was allowed to rest for 5 minutes between each charging and discharging, and the change of battery voltage signal over time was recorded.

[0227] (2) Scanning electron microscopy tests include:

[0228] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and CR2032 coin cells are assembled directly.

[0229] ② Constant current charge-discharge cycle: Using the LAND battery test channel at 0.1mA cm -2 The current density was used for charging and discharging for 1 hour each, and the charging and discharging were repeated 50 times.

[0230] ③ Disassemble the battery, remove the lithium sheet on the lithium-plated (i.e., Li-deposited) side, and use a Regulus 8100 scanning electron microscope for secondary electron imaging to observe the morphology of the deposited lithium metal at 1000x magnification.

[0231] (3) X-ray photoelectron spectroscopy includes:

[0232] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and CR2032 coin cells are assembled directly.

[0233] ② Constant current charge-discharge cycle: Using the LAND battery test channel at 0.1mA cm -2 The current density was used for charging and discharging for 1 hour each, and the charging and discharging were repeated 50 times.

[0234] ③ X-ray photoelectron spectroscopy (XPS) test: The battery was disassembled, and the lithium sheet on the lithium-plated (i.e., Li-deposited) side was removed. XPS test was performed on the lithium sheet using a Thermo Fisher Scientific ESCALA 250Xi, followed by argon ion etching. The etching was performed once every 30 seconds for a total of 4 times. After each etching, a full XPS spectrum test was performed, and a total of 5 sets of XPS full spectrum data were obtained. The content of each element was then analyzed.

[0235] (4) Tafel curve testing includes:

[0236] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and CR2032 coin cells are assembled directly.

[0237] ② Constant current charge-discharge cycle: Using the LAND battery test channel at 0.1mA cm -2 The current density was used for charging and discharging for 1 hour each, and the charging and discharging were repeated 50 times.

[0238] ③ Use the Chenhua CHI650e electrochemical workstation to perform a line scan at a potential of -0.2 to 0.2V and record the change in current (density) with potential.

[0239] ④ Calculation of exchange current density: Take the current density value at the intersection of the tangent line at one end of the Tafel curve and the potential η = 0 as the exchange current density j0.

[0240] (5) AC impedance curve testing includes:

[0241] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The separator uses the solid electrolyte membrane of the corresponding embodiment and comparative example. No electrolyte injection is required, and CR2032 coin cells are assembled directly.

[0242] ② Constant current charge-discharge cycle: Using the LAND battery test channel at 0.1mA cm -2 The current density was used for charging and discharging for 1 hour each, and the charging and discharging were repeated 50 times.

[0243] ③ Using a Chenhua CHI650e electrochemical workstation and a variable-temperature battery oven, the AC impedance spectra of uncycled Li|Li symmetric cells at room temperature and 30℃, 40℃, 50℃, 60℃, and 70℃ at open-circuit voltages were measured, with a frequency range of 1×10⁻⁶. 6 Hz-0.01Hz, amplitude 5mA.

[0244] ④ Use the equivalent circuit Rb(R SEI Q)(R ctBy fitting the AC impedance spectrum to Q)Qw, lg(1 / R) can be plotted. SEI ), lg(1 / R ct The relationship between ) and temperature, and according to the Arrhenius relation lg(1 / R) SEI ) = A + E a,SEI / (RT) and lg(1 / R) ct ) = A + E a,ct The activation energies E of lithium ions crossing the SEI and electrolyte surface were obtained by linear fitting of / (RT). a,SEI With E a,ct In the formula, R is the gas constant R = 8.314 J mol -1 K -1 T is the temperature at the time of measurement, in K, and A is an entropy-dependent temperature-independent constant. It should be noted that the equivalent circuit Rb(R SEI Q1)(R ct Q2) Qw is an electrochemical equivalent circuit model commonly used for fitting the electrochemical impedance spectroscopy (EIS) of lithium metal batteries (especially symmetrical batteries). Its structure can be reduced to a combination of multiple series and parallel resistors and capacitors (or their generalized forms) to simulate the electrochemical behavior of different processes within the battery. Rb (Bulk resistance) is the bulk resistance of the solid electrolyte membrane; R SEI Q1 is the SEI film resistor, and Q1 is the non-ideal capacitance of the SEI film. SEI Q1) that is (R) SEI ||Q1) represents the resistance and capacitance behavior of the solid electrolyte interlayer (SEI) formed at the electrode / electrolyte interface; R ct Q1 is the charge transfer resistor, Q2 is the double-layer capacitance or interface capacitance, (R) ct Q2) that is, (R) ct ||Q2) represents the combination of charge transfer resistance and double-layer capacitance; Qw refers to the Warburg element, representing Li + Diffusion process inside the electrode.

[0245] Table 2 shows the pre-cycle impedance and post-cycle exchange current density of Li|Li symmetric cells assembled with PEO-based polymer electrolytes under different amounts of aluminum acetylacetonate.

[0246] sample Example 1 Example 2 Example 3 Comparative Example 1 Rct(Ω) before the loop 1530 1070 1190 2280 <![CDATA[Exchange current density (mA cm -2 [[ID=2>)]]> 0.0219 0.0282 0.0234 0.0151

[0247] Table 3 shows the AC impedance spectra of Li|Li symmetric cells assembled with PEO-based polymer electrolytes after cycling.

[0248]

[0249]

[0250] As can be seen, in addition to its effect on the polymer matrix, aluminum acetylacetonate additive also plays a crucial role in regulating the compatibility of the electrolyte and the negative electrode.

[0251] Figure 2 SEM morphology characterization of lithium metal in the Li|Li symmetric battery assembled in Example 2 after 50 cycles. Figure 2a The image shows a color image of the lithium anode in the Li|Li symmetric battery assembled in Example 2 after 50 cycles. Figure 2b The image shows the SEM morphology of lithium metal in the Li|Li symmetric battery assembled in Comparative Example 1 after 50 cycles. The upper right corner of the image shows a color image of the lithium anode. It can be seen that in Example 2, the addition of aluminum acetylacetonate additive to the polymer electrolyte significantly reduced lithium dendrites on the anode surface, and there were no obvious signs of side reactions on the lithium anode. However, in Comparative Example 1, the lithium anode surface after cycling showed significantly more dendrites and a completely yellow appearance, indicating severe side reactions.

[0252] Figure 2c The constant current charge-discharge test curves of the Li|Li symmetric cells assembled in Example 2 and Comparative Example 1 are shown. It can be seen that under the action of aluminum acetylacetonate, Example 2 has more stable polarization and significantly extended cycle life, and can stably cycle for more than 2400 hours.

[0253] Figure 2d and Figure 2e X-ray photoelectron spectroscopy (XPS) spectra of lithium metal after cycling in the Li|Li symmetric cells assembled in Comparative Example 1 and Example 2. The SEI on the lithium anode surface in Example 2 shows significantly more fluorine and sulfur elements, which originate solely from TFSI. - Anions are present, thus proving that aluminum acetylacetonate additives help promote anion decomposition, thereby forming a higher-performance SEI on the lithium anode surface, which is beneficial to stabilizing the cycle stability of lithium metal.

[0254] Figure 2f The images show the Tafel curves for Examples 1-3 and Comparative Example 1. It can be seen that the exchange current significantly increased after adding aluminum acetylacetonate to the polymer electrolytes in Examples 1-3. This indicates that adding aluminum acetylacetonate promotes the formation of the SEI on the lithium metal surface, resulting in better ion transport kinetics. The highest exchange current density was observed when the aluminum acetylacetonate addition was 5%, further demonstrating that adding an appropriate amount of aluminum acetylacetonate to the polymer electrolyte resulted in the best ion transport kinetics for the SEI formed on the lithium metal surface.

[0255] Figure 2gThe AC impedance test results (without cycling) of the Li|Li symmetric cells assembled in Examples 1-3 and Comparative Example 1 are shown, which are 1530Ω, 1070Ω, 1190Ω, and 2280Ω, respectively. This also demonstrates that the addition of aluminum acetylacetonate can significantly reduce the lithium-ion interfacial transport impedance R. ct This helps reduce the polarization of lithium-ion batteries and improve energy efficiency. Furthermore, when aluminum acetylacetonate is added at 5%, it exhibits the lowest lithium-ion interfacial transport impedance R. ct This also shows that adding an appropriate amount of aluminum acetylacetonate to the polymer electrolyte can effectively reduce the interfacial transport resistance.

[0256] Figure 2h The figure shows the EIS curves of the Li|Li symmetric cells assembled in Example 2 and Comparative Example 1 after 50 cycles at different test temperatures. The R values ​​at each temperature were obtained by fitting the curves. ct and R SEI Impedance values. Fitting these two impedances using the Arrhenius relation reveals that, in Example 2, due to the addition of aluminum acetylacetone additive to the polymer electrolyte, its Ea... ct and Ea SEI The activation energies were significantly lower, at 75.2 kJ / mol and 73.6 kJ / mol, respectively, compared to 78.9 kJ / mol and 81.9 kJ / mol under the conditions of Comparative Example 1. This indicates that in the battery assembled in Example 2, the energy barrier for lithium ions to cross the electrolyte-SEI interface and migrate within the SEI is lower, suggesting superior interfacial performance and better lithium-ion transport capabilities.

[0257] (III) The polymer electrolyte modified with additives was applied to Li|lithium iron phosphate batteries. The polymer electrolytes of Example 2 and Comparative Example 1 were used to assemble Li|lithium iron phosphate batteries and cycle tests were conducted under different conditions, including rate tests at 60°C, long cycle tests at 0.5C and 2C at 60°C, and long cycle tests at 0.2C at 30°C.

[0258] (1) Li|Li iron phosphate battery cycle test includes:

[0259] ① Assembly of lithium iron phosphate button batteries: A slurry is prepared according to a mass ratio of lithium iron phosphate: conductive carbon black (SP): PVDF = 80:1:1, and then coated onto a 20µm thick aluminum foil to create a positive electrode sheet with an areal density of 1-2 mg / cm³. 2 The negative electrode uses a lithium sheet (500μm), and the separator uses the tested solid electrolyte membrane. No electrolyte injection is required, and the CR2032 coin cell is assembled directly.

[0260] ② Test using the LAND battery test channel:

[0261] 1) Rate discharge performance test at 60℃: The lithium iron phosphate button batteries assembled in Example 2 and Comparative Example 1 were tested using a Blue Electric tester. The voltage range was 2.5-3.8V. Formation was performed first with a current of 0.05C, followed by 5 charge-discharge cycles each with currents of 0.1C, 0.2C, 0.5C, 1C, and 2C. After the cycle, the batteries were continuously charged and discharged at a current of 0.1C. After each constant current charge to 3.8V, constant voltage charge was performed. The charging cutoff current was 0.025C.

[0262] 2) Cyclic performance test at 60℃ and 0.5C: The lithium iron phosphate button batteries assembled in Example 2 and Comparative Example 1 were tested using a Blue Electric Tester. The voltage range was 2.5-3.8V. Formation was performed first with a current of 0.05C, and then continuous charge and discharge was performed at a current of 0.5C. After each constant current charge to 3.8V, constant voltage charge was performed. The charging cut-off current was 0.025C.

[0263] 3) 2C cycle performance test at 60℃: The lithium iron phosphate button batteries assembled in Example 2 and Comparative Example 1 were tested using a Blue Electric Tester. The voltage range was 2.5-3.8V. Formation was performed first with a current of 0.05C, and then continuous charge and discharge was performed at a current of 2C. After constant current charging to 3.8V each time, constant voltage charging was performed. The charging cut-off current was 0.025C.

[0264] 4) Cyclic performance test at 30℃ and 0.2C: The lithium iron phosphate button batteries assembled in Example 2 and Comparative Example 1 were tested using a Blue Electric Tester. The voltage range was 2.5-3.8V. Formation was performed first with a current of 0.05C, followed by continuous charge and discharge at a current of 0.2C. After each constant current charge to 3.8V, constant voltage charge was performed. The charging cutoff current was 0.025C.

[0265] Table 4 shows the rate performance of Li|lithium iron phosphate (LFP) batteries assembled with PEO-based polymer electrolytes.

[0266]

[0267] The results of rate performance tests conducted on Li / LFP assemblies assembled in Example 2 and Comparative Example 1 are as follows. Figure 3a See Table 4. The battery of Example 2 achieved a capacity of 170.5 mAh g at 0.1C, 0.2C, 0.5C, 1C, and 2C. -1 168.4mAh g -1 164.8mAh g -1 161.1mAh g -1 127.2mAh g -1The battery in Comparative Example 1 achieved capacities of 166.6 mAh g at 0.1C, 0.2C, 0.5C, 1C, and 2C. -1 164.7mAh g -1 156.4mAh g -1 131.9mAh g -1 79.9mAh g -1 The Li|LFP battery assembled in Example 2 still has a capacity of 127.2 mAh g⁻¹ at a high 2C rate. -1 The higher specific capacity of [the sample], while the comparative sample 1 has only 79.9 mAh g. -1 Example 2 showed significantly higher performance than Comparative Example 1. Specifically, the solid-state battery assembled in Example 2 exhibited a discharge specific capacity at 1C and 2C levels that was 29.2 mAh g higher than that of Comparative Example 1. -1 and 47.3mAh g -1 As can be seen, the addition of aluminum acetylacetone to the polymer electrolyte of the present invention results in a solid-state battery with a significantly higher specific capacity at high rates, exhibiting superior rate performance.

[0268] Figure 3b The voltage-capacity curves of Example 2 and Comparative Example 1 at various rates of 0.1C, 0.2C, 0.5C, 1C, and 2C are shown. It can be seen that the Li|LFP battery with added aluminum acetylacetonate has a smaller voltage plateau spacing at each rate, indicating that the polarization of the battery is significantly reduced.

[0269] Table 5 shows the cycle performance of Li|lithium iron phosphate (LFP) batteries assembled with PEO-based polymer electrolytes.

[0270]

[0271] Figure 3c The cycling performance of the Li|lithium iron phosphate batteries assembled with polymer electrolytes of Example 2 and Comparative Example 1 at 0.5C and 60°C is shown. The first-cycle discharge specific capacity of the batteries in Example 2 and Comparative Example 1 is 157.1 mAh g, respectively. -1 and 159.06mAh g -1 The specific capacity of Comparative Example 1 was slightly higher than that of Example 2. However, when the battery was cycled 200 times at 2.5-3.8V, the discharge specific capacity of the batteries in Example 2 and Comparative Example 1 was 153.7 mAh g, respectively. -1 and 149.9mAh g -1 Example 2 showed a 3.8 mAh / g increase compared to Comparative Example 1. -1 After 500 cycles, the discharge specific capacity of Example 2 and the discharge specific capacity of Comparative Example 1 were 149.4 mAh g, respectively. -1 and 124.4mAh g-1 The capacity retention rates were 95.12% and 78.22%, respectively. Example 2 showed a discharge specific capacity 25 mAh higher than Comparative Example 1. -1 The capacity retention rate is 16.9% higher. A significant difference exists in the discharge specific capacity between the two. It can be seen that the battery assembled using the polymer electrolyte of Example 2 can stably cycle 800 times, and the discharge specific capacity is still as high as 143.8 mAh g⁻¹. -1 The capacity retention rate reached 91.59%, while the specific capacity of the battery assembled using the polymer electrolyte of Comparative Example 1 began to rapidly decline after 500 cycles. This indicates that the addition of aluminum acetylacetonate to the polymer electrolyte of the present invention can effectively improve the cycle stability of the battery. This is because aluminum acetylacetonate can promote the decomposition of anions, thereby regulating the performance of the electrode-electrolyte interface, which is beneficial to improving the overall cycle stability of the battery.

[0272] Figure 3d The results of charge-discharge cycle tests conducted at 60°C and 2C on batteries assembled with the polymer electrolytes of Example 2 and Comparative Example 1 are shown. It can be seen that the first-cycle discharge specific capacity of the batteries in Example 2 and Comparative Example 1 is 129.6 mAh g⁻¹. -1 and 95mAh g -1 Example 2 has 34.6 mAh higher than Comparative Example 1. -1 Therefore, the polymer electrolyte-assembled battery of this invention already exhibits superior performance in the first week of charge-discharge at high rates. This is because the addition of aluminum acetylacetonate in this invention promotes lithium-ion transport and results in better lithium-ion transport kinetics. When the battery is cycled 150 times at 2.5-3.8V, the discharge specific capacity of the batteries in Example 2 and Comparative Example 1 is 128.22 mAh g, respectively. -1 and 92.67mAh g -1 Example 2 has 35.55 mAh higher than Comparative Example 1. -1 The difference in discharge specific capacity between the two further increased. The capacity retention rates of the batteries in Example 2 and Comparative Example 1 were 98.93% and 97.57%, respectively, with a difference of only 1.36%, which is not significant. Figure 3d As can be seen, after 150 charge-discharge cycles, the discharge specific capacity of Example 2 remained relatively stable, while the discharge specific capacity of Comparative Example 1 showed a significant decrease. When the charge-discharge cycle reached 300 cycles, the specific capacity of the battery in Example 2 was 119.98 mAh g. -1 The capacity retention rate is as high as 92.57%, while the discharge specific capacity of Comparative Example 1 is 47.39 mAh g. -1 The capacity retention rate was only 49.88%, and the discharge specific capacity of Example 2 was 72.59 mAh g higher than that of Comparative Example 1.-1 The capacity retention rate was 42.69% higher. The battery performance of Example 2 was significantly higher than that of Comparative Example 1. This is due to the superior lithium-ion transport kinetics of the SEI formed by the reaction of aluminum acetylacetonate and anions in the polymer electrolyte of Example 2, as well as the performance of the electrode-electrolyte interface after the addition of aluminum acetylacetonate, which is beneficial to improving the overall cycle stability of the battery.

[0273] Figure 3e The results of charge-discharge cycle tests conducted at 30°C and 0.2C on batteries assembled with the polymer electrolytes of Example 2 and Comparative Example 1 are shown. It can be seen that the first-cycle discharge specific capacity of the batteries in Example 2 and Comparative Example 1 is 155 mAh g⁻¹. -1 and 41.43mAh g -1 Example 2 showed a 113.57 mAh / g increase compared to Comparative Example 1. -1 Therefore, in terms of charge-discharge performance at room temperature, the battery assembled with the aluminum acetylacetonate-modified polymer electrolyte of this invention significantly outperforms existing PEO batteries. When the batteries were cycled 80 times at 2.5-3.8V, the discharge specific capacity of the batteries in Example 2 and Comparative Example 1 was 149.01 mAh g, respectively. -1 and 104.83mAh g -1 Example 2 showed a 44.18 mAh / g increase compared to Comparative Example 1. -1 The battery in Comparative Example 1 experienced a short circuit after 80 cycles at room temperature, resulting in battery failure. When the battery in Example 2 underwent 200 charge-discharge cycles, its discharge specific capacity was 146.1 mAh g. -1 The capacity retention rate is as high as 96.27%. Since aluminum acetylacetonate can significantly improve the ionic conductivity of polymer electrolytes, the battery in Example 2 can also maintain high capacity and stable cycling when charged and discharged at room temperature, which is not possible with current PEO-based electrolytes.

[0274] (iv) In order to verify the universality of aluminum acetylacetonate additive in different systems and its effectiveness in promoting anion decomposition, in Example 4, aluminum acetylacetonate was also used as an additive to modify the PVDF / LiFSI system with high ionic conductivity. The PVDF / LiFSI membrane without additive was used as a control group (Comparative Example 2) to test the basic electrochemical properties, including: ionic conductivity test, electrochemical window test, and ion transference number test. The above test methods are the same as the test conditions of the PEO-based electrolyte mentioned above.

[0275] Table 6 summarizes the test data for the basic properties of PVDF-based polymer electrolytes.

[0276]

[0277] In Example 4, the amount of aluminum acetylacetone additive added was 5 wt% relative to the polymer electrolyte matrix, while Comparative Example 2 did not contain acetylacetone additive. As shown in Table 6, and in conjunction with... Figure 4a It can be seen that the ionic conductivity of the polymer electrolyte in Example 4 reaches 5.68 × 10⁻⁶ at 30°C. -4 S / cm, reaching 9.54×10 at 40℃ -4 S / cm, reaching 1.32×10 at 50℃ -3 S / cm, reaching 1.73×10 at 60℃ -3 S / cm, reaching 2.23×10 at 70℃ -3 S / cm; The ionic conductivity of the polymer electrolyte in Comparative Example 2 reached 3.83 × 10⁻⁶ at 30 °C. -4 S / cm, reaching 5.41×10 at 40℃. -4 S / cm, reaching 6.68×10 at 50℃ -4 S / cm, reaching 1.04×10 at 60℃ -3 S / cm, reaching 1.42×10 at 70℃ -3 S / cm. For example... Figure 4a As shown, with an appropriate amount of aluminum acetylacetonate added, the ionic conductivity of the PVDF-based polymer electrolyte was significantly improved, approaching or exceeding 0.1 mS / cm. -1 In summary, similar to PEO-based polymer electrolytes, the ionic conductivity of PVDF-based polymer electrolytes increases upon the addition of aluminum acetylacetonate. The PVDF / LiFSI system in Example 4 exhibits very high room-temperature ionic conductivity (~0.5 mS / cm) due to the residual DMF solvent. -1 However, DMF has more serious side reaction problems on the negative electrode side. In contrast, the addition of a certain amount of aluminum acetylacetonate to the PVDF-based polymer electrolyte of the present invention can effectively improve the ionic conductivity and has almost no side reactions on the negative electrode side. Figure 4a The ionic conductivity test results shown indicate that the ionic conductivity of Example 4 was significantly improved compared to Comparative Example 2 after the addition of aluminum acetylacetonate.

[0278] Figure 4b The electrochemical window test results of the PVDF-based polymer electrolyte modified with aluminum acetylacetonate in Example 4 and the PVDF-based polymer electrolyte in Comparative Example 2 are shown. The electrochemical windows of Example 4 and Comparative Example 2 are 4.7V and 4.2V, respectively. It can be seen that adding aluminum acetylacetonate to the PVDF-based polymer electrolyte increases the electrochemical window of the polymer electrolyte by 0.5V, significantly improving the electrochemical window of the PVDF-based polymer electrolyte.

[0279] like Figure 4c and Figure 4d As shown, the ion transport numbers of Comparative Example 2 and Example 4 were 0.32 and 0.57, respectively, indicating that the addition of aluminum acetylacetonate to the PVDF-based polymer electrolyte can significantly improve the ion transport number.

[0280] (v) To demonstrate the improvement in electrochemical performance of the modified PVDF-based electrolyte, Li|Li symmetric batteries and Li|LiFePO4 batteries were assembled using Example 4 and Comparative Example 2, respectively, and cycle tests were conducted. Specifically, the tests included: long cycle test of Li|Li symmetric battery, cycle test of Li|Li symmetric battery at different current densities, and long cycle test at 0.5C and 2C at 30°C.

[0281] (1) Cyclic testing of Li|Li symmetric cells includes:

[0282] ① Assembly of Li|Li symmetric cells: Lithium sheets (500μm thick) are used for both positive and negative electrodes. The solid electrolyte membrane tested is used for the separator. No electrolyte injection is required. CR2032 coin cells are assembled directly.

[0283] ② Constant current charge-discharge cycle:

[0284] 1) Long-cycle testing: Using the LAND battery test channel at 0.1mA cm -2 The battery was charged and discharged at the current density for 1 hour each, and the charging and discharging were repeated continuously. The battery was allowed to rest for 5 minutes between each charge and discharge, and the change of battery voltage signal over time was recorded.

[0285] 2) Cyclic testing of Li|Li symmetric cells at different current densities: Using the LAND cell test channel at current densities of 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4, and 5 mA / cm². -2 The current density for both charging and discharging is 1 mAh cm⁻¹. -2 Between each charge and discharge cycle, the battery was allowed to stand for 5 minutes, and the change in battery voltage signal over time was recorded.

[0286] (2) Li|Li iron phosphate battery cycle test includes:

[0287] ① Assembly of lithium iron phosphate button batteries: Lithium iron phosphate: SP:PVDF = 80:1:1 is homogenized into a slurry, which is then coated onto a 20µm thick aluminum foil to produce a positive electrode with an areal density of 1-2 mg / cm³. 2 The negative electrode uses a lithium sheet (500μm), and the separator uses the tested solid electrolyte membrane. No electrolyte injection is required, and the CR2032 coin cell is assembled directly.

[0288] ② Test using the LAND battery test channel:

[0289] 1) Cyclic performance test at 30℃ and 0.5C: The lithium iron phosphate button batteries assembled in Example 4 and Comparative Example 2 were tested using a Blue Electric Tester. The voltage range was 2.5-3.8V. Formation was performed first with a current of 0.05C, and then continuous charge and discharge was performed at a current of 0.5C. After each constant current charge to 3.8V, constant voltage charge was performed. The charging cut-off current was 0.025C.

[0290] 2) 2C cycle performance test at 30℃: The lithium iron phosphate button batteries assembled in Example 2 and Comparative Example 1 were tested using a Blue Electric Tester. The voltage range was 2.5-3.8V. Formation was performed first with a current of 0.05C, and then continuous charge and discharge was performed at a current of 0.5C. After each constant current charge to 3.8V, constant voltage charge was performed. The charging cut-off current was 0.025C.

[0291] Table 7 shows the cycle performance of Li|lithium iron phosphate batteries assembled with PVDF-based polymer electrolytes.

[0292]

[0293] Figure 5a The cycling performance of the Li|Li symmetric cell at 30℃ under low current density was shown. It was found that the polarization overpotential of the PVDF-based electrolyte significantly decreased after the addition of aluminum acetylacetonate, dropping from ~0.025V to 0.01V. Figure 5b The figure shows the cycling of a Li|Li symmetric battery from low to high current density. As can be seen from the figure, Comparative Example 2 cannot withstand current densities exceeding 2 mA cm⁻¹. -2 At a current density that causes a sharp increase in polarization and battery failure, Example 4 can withstand the current density, demonstrating its superior negative electrode stability and interfacial ion transport kinetics.

[0294] Figure 5c The figures show the cycle performance of the Li|lithium iron phosphate batteries assembled with polymer electrolytes in Example 4 and Comparative Example 2 at 30°C and 0.5C. The first-cycle discharge specific capacity of the batteries in Example 4 and Comparative Example 2 was 152.9 mAh g, respectively. -1 and 153.4mAh g -1 The specific capacity of Comparative Example 2 was slightly higher than that of Example 4. However, when the battery was cycled 50 times at 2.5-3.8V, the discharge specific capacity of the batteries in Example 4 and Comparative Example 2 was 146.1 mAh g, respectively. -1 and 144.1mAh g -1 Example 4 showed a 2.0 mAh / g increase compared to Comparative Example 2. -1 After 120 cycles, the discharge specific capacity of the battery in Example 4 and the discharge specific capacity of the battery in Comparative Example 2 were 143 mAh g, respectively. -1 and 138.56mAh g-1 The capacity retention rates were 93.53% and 90.33%, respectively. Example 4 showed a discharge specific capacity 4.44 mAh g higher than Comparative Example 2. -1 The capacity retention rate is 3.2% higher. This indicates that the addition of aluminum acetylacetonate to the PVDF-based polymer electrolyte of the present invention can improve the cycle stability of the battery.

[0295] Figure 5d The results of charge-discharge cycle tests conducted at 30°C and 2C on the polymer electrolyte-assembled batteries of Example 4 and Comparative Example 2 are shown. It can be seen that the first-cycle discharge specific capacity of the batteries of Example 4 and Comparative Example 2 is 135.4 mAh g⁻¹. -1 and 132.7mAh g -1 Example 4 showed a 2.7 mAh / g increase compared to Comparative Example 2. -1 When the batteries were cycled 50 times at 2.5-3.8V, the discharge specific capacity of the batteries in Example 4 and Comparative Example 2 was 140.4 mAh g, respectively. -1 and 129.4mAh g -1 Example 4 has 11 mAh higher than Comparative Example 2. -1 The difference in discharge specific capacity between the two increases, and the capacity retention rates of the batteries in Example 4 and Comparative Example 2 are greater than 100% and 97.51%, respectively. From Figure 5d As can be seen, after 150 charge-discharge cycles, the specific capacity of the battery in Example 4 is 140.4 mAh g. -1 From 50 to 150 revolutions, the battery's specific capacity did not decrease at all, while the discharge specific capacity of Comparative Example 2 was 121.36 mAh g. -1 The capacity retention rate was 91.45%. The battery performance of Example 4 was significantly higher than that of Comparative Example 2, which was also due to the superior lithium-ion transport kinetics of the SEI formed after the reaction of aluminum acetylacetonate additive with anions, as well as the performance of the electrode-electrolyte interface after the addition of aluminum acetylacetonate, which is conducive to improving the overall cycle stability of the battery at high rates.

[0296] (vi) To demonstrate the modification effects of different acetylacetone complexes on polymer-based electrolytes, stainless steel|stainless steel, Li|Li symmetric batteries and Li|stainless steel batteries were also assembled for Examples 5 and 6, which used zinc acetylacetone and zirconium acetylacetone as additives. Ionic conductivity, electrochemical window and lithium symmetric battery were tested respectively, using the same testing methods as above. These results were compared with Example 2 and Comparative Example 1.

[0297] Table 8 compares the modification effects of different acetylacetone complexes.

[0298]

[0299] Ionic conductivity for example Figure 6a As shown, compared to the PEO matrix, the ionic conductivity of the polymer electrolyte was higher when 5% aluminum acetylacetonate and zinc acetylacetonate were added, respectively, than that of the polymer electrolyte without additives; however, when 5% zirconium acetylacetonate was added, the ionic conductivity of the polymer electrolyte decreased slightly (3.03 × 10⁻⁶ at 30℃). -5 S cm -1 This may be because the zirconium acetylacetonate molecule has four ligands, and its steric hindrance is too large after dissolving in the polymer phase, which to some extent hinders the transport of lithium ions.

[0300] Furthermore, the effect of using zinc acetylacetonate as an additive on improving ionic conductivity was not as significant as that of aluminum acetylacetonate (4.59 × 10⁻⁶ at 30℃). -5 S cm -1 This is because aluminum acetylacetonate has a stronger Lewis acidity at its aluminum ion center, allowing for more effective interaction with the polymer matrix. Since few metal ions have a Lewis acidity exceeding that of aluminum ions, aluminum acetylacetonate is the optimal additive for acetylacetonate complexes.

[0301] Furthermore, the nickel and copper acetylacetone used in Examples 7 and 8 are less effective than aluminum acetylacetone in improving ionic conductivity, with an ionic conductivity at 50°C on the order of approximately 10. -4 S·cm -1 Slightly lower than Example 2. Furthermore, the acetylacetone ligand, due to the strong electron-withdrawing properties of its carbonyl group, can enhance the Lewis acidity of the metal center, thereby more effectively promoting the interaction with the polymer matrix. The complexes used in Examples 9 and 10 have weaker Lewis acidity at their metal centers, and their ability to enhance polymer-metal interactions is lower than that of Example 2; therefore, their ionic conductivity at 50°C is on the order of approximately 10. -4 S·cm -1 Magnitude.

[0302] The linear sweep voltammetry (LSV) test results of polymer electrolytes with the addition of 5 wt% of different acetylacetone complexes are as follows: Figure 6b As shown in the figure, the addition of the acetylacetone complex can significantly improve the electrochemical window of the polymer electrolyte. Furthermore, the polymer electrolytes of Examples 7-10, with the aforementioned complexes added, also exhibit similar Lewis acidic metal centers, which can regulate polymer segments through Lewis acid-base interactions, stabilizing the negatively charged functional groups and their surrounding atoms. Therefore, their electrochemical windows are still higher than those of Comparative Example 1.

[0303] The cycling performance of Li|Li symmetric batteries was tested after adding 5 wt% of different acetylacetone complexes to the polymer electrolyte. The results are as follows: Figure 6c As shown in the figure, the polymer electrolyte with added aluminum acetylacetonate exhibits the most stable electrochemical polarization and cycle life, with stable cycling exceeding 2400 h.

[0304] (vii) To demonstrate the importance of plasticizers and fillers dispersed in the battery, ionic conductivity and electrochemical window were tested using Comparative Example 3, which used nano-sized filler LATP as an additive, and Comparative Example 4, which did not contain plasticizers. The tests were also performed using Example 11, with the same testing methods as above. These results were compared with those of Example 2, which had already been tested.

[0305] Table 9 compares the performance with and without plasticizers and with and without solid electrolytes.

[0306]

[0307]

[0308] Ionic conductivity for example Figure 7a As shown, Comparative Example 3 used nano-sized oxide solid electrolyte LATP as a filler, which can improve the ionic conductivity of the electrolyte to a certain extent, but the effect is not as good as aluminum acetylacetonate. In addition, without the use of plasticizers, the room temperature ionic conductivity of Comparative Example 4 is only 10. -6 Scm -1 The plasticizing effect was significantly different from that of Comparative Example 1 and Example 2 after heating, even with the addition of plasticizers. This demonstrates that from a practical perspective, the addition of plasticizers still offers certain advantages, and introducing plasticizers is a feasible method to significantly improve ionic conductivity. Furthermore, Example 12 and Comparative Example 5, prepared by in-situ polymerization, achieved similar plasticizing effects by using monomers with low polymerization degrees, achieving an ionic conductivity of up to 10 at 30°C. -4 Up to 10 -3 S·cm -1 The order of magnitude. In Example 12, the interface optimization effect resulting from the introduction of aluminum acetylacetonate further improved cycle performance, demonstrating excellent overall performance advantages. Furthermore, in Example 11, although no plasticizer was added, 3% aluminum acetylacetonate was added, yet higher ionic conductivity was still achieved than in Comparative Example 4, further verifying the effectiveness of aluminum acetylacetonate in improving interfacial ionic conductivity.

[0309] Figure 7bThe electrochemical window test results are shown. It can be seen that the presence of the plasticizer succinate can improve the overall electrochemical oxidation resistance of the electrolyte by utilizing its excellent high voltage stability. Comparative Example 4, without plasticizer, experienced severe electrochemical oxidation and a surge in current signal when immersed at <4V. While the addition of aluminum acetylacetonate alleviated the problem, severe electrochemical oxidation still occurred at ~4.5V. The addition of LATP further broadened the electrochemical window, but its effect was still not as good as aluminum acetylacetonate. The polymer electrolyte in Example 11 achieved an electrochemical window of 4.41V, which is 0.66V higher than that of Comparative Example 4. This indicates that, even without plasticizers, aluminum acetylacetonate can significantly improve the electrochemical window.

[0310] Figure 7c The figure shows a comparison of the cycling performance of Comparative Example 1 and Comparative Example 3 with LATP. By comparing the cycling performance graphs of Comparative Example 1 and Comparative Example 3, it is unexpected that the Li|lithium iron phosphate battery assembled with the electrolyte after adding LATP has worse cycling performance than the one without LATP. Its capacity rapidly decays after 100 cycles. This may be due to the poor contact at the electrolyte-electrode interface caused by the severe aggregation of LATP particles.

[0311] Figure 7d The nano-sized LATP material used exhibits a clear tendency to aggregate. When incorporated into the electrolyte (Fig. 7e, f), it also aggregates in the electrolyte, forming numerous rigid protrusions and depressions on the surface, leading to rapid deterioration of electrode-electrolyte contact and capacity decay during cycling.

[0312] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A polymer electrolyte containing a soluble organometallic complex, characterized in that, The polymer electrolyte containing a soluble organometallic complex comprises: a polymer matrix, a lithium salt, and an organometallic complex; The organometallic complex is uniformly distributed in the polymer matrix, forming a molecular-level mixture; the mass ratio of the organometallic complex to the polymer matrix is ​​3:100-10:

100. The surface of the organometallic complex has active sites, which act as Lewis acids and interact with polymer segments or anions in lithium salts that are Lewis bases to form coordination structures.

2. The polymer electrolyte according to claim 1, characterized in that, The organometallic complex includes one or more of the following: acetylacetone complex, isopropanol complex, and ethoxy compounds; The polymer matrix includes one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), polyvinylidene chloride (PVDC), poly(polyethylene glycol monomethyl ether) (PEGMEA), polyaramid, polyimide, polyvinylidene fluoride, polytetrafluoroethylene, or single-ion conductor polymer electrolytes (SICPEs). The lithium salt includes one or more of inorganic lithium salts or organic lithium salts; the lithium salt is preferably a lithium salt containing a sulfonyl group and / or a carbonyl group; more preferably, the lithium salt specifically includes one or more of lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate; the mass ratio of the lithium salt to the polymer matrix is ​​30:100-100:

100.

3. The polymer electrolyte according to claim 1 or 2, characterized in that, The organometallic complex includes an acetylacetone complex; preferably, the acetylacetone complex specifically includes one or more of aluminum acetylacetone, nickel acetylacetone, copper acetylacetone, zinc acetylacetone, and zirconium acetylacetone.

4. The polymer electrolyte according to claim 1, characterized in that, The polymer electrolyte further includes a supporting material; the supporting material includes one or more of the following: a base membrane, nonwoven fabric, glass fiber, and fiber composite material; the supporting material is preferably a porous supporting material, more preferably a porous base membrane; the porosity of the porous supporting material is 50%-90%; and / or, The polymer electrolyte further includes one or more of the following: film-forming agent, plasticizer, and filler; The film-forming agent includes one or more of fluoroethylene carbonate (FEC), lithium difluorooxalate borate (LiDFOB), and lithium difluorophosphate; the mass ratio of the film-forming agent to the polymer matrix is ​​3:100-10:

100. The plasticizer includes one or more of succinic acid, tetraethylene glycol dimethyl ether, ethylene carbonate EC, ethylene ethylene carbonate VEC, ethylene ethylene carbonate VC, N,N-dimethylformamide DMF, and N,N-dimethylacetamide DMAc; the mass ratio of the plasticizer to the polymer matrix is ​​15:100-40:

100. The filler includes inorganic fillers and / or organic fillers; specifically, it includes active fillers and / or inert fillers, wherein the active filler is an inorganic solid electrolyte with ion-conducting capability, including one or more of perovskite type, NASICON type, garnet type, oxide glass and sulfide glass; the inert filler is a material without ion-conducting capability, including one or more of SiO2, ZrO2, Al2O3, TiO2, clay, metal-organic framework compound (MOF), covalent organic framework (COF); the mass ratio of the filler to the polymer matrix is ​​1:100-60:

100.

5. A method for preparing a polymer electrolyte containing a soluble organometallic complex according to any one of claims 1-4, characterized in that, The preparation method includes: solution casting or in-situ polymerization; The solution casting method includes: uniformly mixing a polymer matrix, lithium salt, organometallic complex, and solvent in a mass ratio of 100:30-100:3-10:1000-2000 to form a polymer solution, and drying the polymer solution to obtain the polymer electrolyte; wherein the organometallic complex is dissolved in the polymer solution; The in-situ polymerization method includes: mixing polymer monomers, lithium salts, organometallic complexes, and initiators in a mass ratio of 100:20-80:1-5:0.2-3 to form a polymer precursor solution, and initiating polymerization on the polymer precursor solution to obtain the polymer electrolyte; wherein the organometallic complex is dissolved in the polymer precursor solution.

6. The preparation method according to claim 5, characterized in that, In the solution casting method, the polymer solution further includes one or more of the following: a film-forming agent, a plasticizer, and a filler; the mass ratio of the film-forming agent to the polymer matrix is ​​3:100-10:100; the mass ratio of the plasticizer to the polymer matrix is ​​15:100-40:100; and the mass ratio of the filler to the polymer matrix is ​​1:100-60:

100. In the in-situ polymerization method, the polymer precursor solution further includes one or more of the following: a film-forming agent, a plasticizer, and a filler; the film-forming agent accounts for 1%-5% of the polymer precursor solution by mass; the plasticizer accounts for 10%-40% of the polymer precursor solution by mass; and the filler accounts for 1%-5% of the polymer precursor solution by mass. The film-forming agent includes one or more of FEC, LiDFOB, and lithium difluorophosphate; The plasticizer includes one or more of succinic anhydride, tetraethylene glycol dimethyl ether, EC, VEC, VC, DMF, and DMAc; The filler includes inorganic fillers and / or organic fillers; specifically, it includes active fillers and / or inert fillers, wherein the active filler is an inorganic solid electrolyte with ion-conducting capability, including one or more of perovskite type, NASICON type, garnet type, oxide glass and sulfide glass; the inert filler is a material without ion-conducting capability, including one or more of SiO2, ZrO2, Al2O3, TiO2, clay, metal-organic framework compound (MOF), and covalent organic framework (COF).

7. The preparation method according to claim 5, characterized in that, In the solution casting method, the solvent includes one or more of the following: nitrile solvents, amide solvents, sulfonate solvents, phosphate solvents, and sulfone solvents; The process of drying the polymer solution to obtain the polymer electrolyte specifically includes: The polymer solution is uniformly coated onto one or both sides of a support material and then dried and cured to obtain the polymer electrolyte; or... The polymer solution is uniformly coated onto the surface of the coating substrate material and then dried and cured. The dried and cured polymer electrolyte is then separated from the coating substrate material to obtain the polymer electrolyte.

8. The preparation method according to claim 5, characterized in that, In the in-situ polymerization method, the polymer monomers include any one or more of the following: ethylene oxide, propylene oxide, 1,3-dioxane, vinylidene fluoride, vinylidene chloride, vinylene carbonate, ethylene ethylene carbonate, 1,3-propanesulfonate lactone, methyl methacrylate, ethyl acrylate, 1,6-hexanediol diacrylate, 2,2,2-trifluoroethyl acrylate, butyl acrylate, acrylic acid, 2,2,3,4,4,4-hexafluoroacrylate butyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, acrylic acid, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, dodecafluoroheptyl acrylate, N,N'-methylenebisacrylamide, pentaerythritol glycidyl ether, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, methyl vinyl sulfone, vinyltrimethoxysilane, diethyl vinylphosphonate, acrylonitrile, polyethylene glycol monomethyl ether acrylate, and oligomers of the above components. The process of initiating polymerization of the polymer precursor solution to obtain the polymer electrolyte specifically includes: The polymer precursor solution is uniformly coated onto one or both sides of a support material, and in-situ polymerization is initiated by light and / or heat to obtain the polymer electrolyte; or... The polymer precursor solution is uniformly coated onto the surface of the coating substrate material, and in-situ polymerization is initiated by light and / or heat. The polymer electrolyte is then separated from the coating substrate material to obtain the polymer electrolyte.

9. An energy storage device, characterized in that, The energy storage device comprises: a polymer electrolyte containing a soluble organometallic complex as described in any one of claims 1-4, or a polymer electrolyte containing a soluble organometallic complex prepared by any one of claims 5-8.

10. The energy storage device according to claim 9, characterized in that, The energy storage device includes: lithium battery, battery cell or battery pack.